Alpha-nucleated propylene / ethylene / 1-butene terpolymer compositions for blown and cast films

By adding an α nucleating agent to the propylene/ethylene/1-butene terpolymer to form an α-nucleated single-phase propylene terpolymer composition, the problem of difficulty in taking into account both mechanical properties and sealing properties in the prior art is solved, and the effect of improving mechanical properties and maintaining good sealing properties is achieved.

CN119744282APending Publication Date: 2025-04-01BOREALIS AG
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202380061133.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-08-23
Filing Date
2023-08-22
Publication Date
2025-04-01

AI Technical Summary

Technical Problem

Existing propylene/ethylene/1-butene terpolymers have difficult challenges in terms of low sealing starting temperature, high thermal viscosity and low extractables, especially in the difficult balance between sealing and mechanical properties in the food packaging field.

Method used

Using an α-nucleated single-phase propylene terpolymer composition, by adding one or more α nucleating agents, including particulate α nucleating agents, to the propylene/ethylene/1-butene random terpolymer, a film with improved mechanical and optical properties is formed while maintaining good sealing properties.

Benefits of technology

The mechanical properties of the film are achieved without sacrificing sealing properties and optical properties, especially maintaining good sealing properties within a wide temperature window.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005279658980000121
    Figure BDA0005279658980000121
  • Figure BDA0005279658980000151
    Figure BDA0005279658980000151
  • Figure BDA0005279658980000171
    Figure BDA0005279658980000171
Patent Text Reader

Abstract

An alpha-nucleated, single-phase propylene terpolymer composition (PC) having an ethylene content in the range of from 0.75 to 4.0 mol%, a 1-butene content in the range of from 2.0 to 7.5 mol%, an MFR2 in the range of from 1.0 to 35 g / 10 min, a melting temperature in the range of from 125 to 140 DEG C and a crystallization temperature in the range of from 95 to 115 DEG C, the alpha-nucleated, single-phase propylene terpolymer composition (PC) having an ethylene content in the range of from 0.75 to 4.0 mol%, a 1-butene content in the range of from 2.0 to 7.5 mol%, an MFR2 in the range of from 1.0 to 35 g / 10 min, wherein the alpha-nucleated single phase propylene terpolymer composition (PC) further has: a) a 1.5 N hot stick sealing process window measured on a 50 [mu] m blown film sample in the range of 15 to 25 DEG C, or b) a 1.5 N hot stick sealing process window measured on a 50 [mu] m cast film sample in the range of 20 to 30 DEG C.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to an α-nucleated single-phase propylene terpolymer composition (PC), articles, especially films, comprising said composition, and a process for producing said composition. Background Art

[0002] Propylene / ethylene / 1-butene terpolymers represent the gold standard for film applications when low seal initiation temperature (SIT), high hot tack and low extractables (for food industry safety) are required. This combination of desirable features is extremely difficult to achieve with other types of polyolefins.

[0003] It is well known that the most direct way to improve (i.e. reduce) SIT is to add higher amounts of comonomers, especially 1-butene; however, it is also well known that this will lead to a higher xylene soluble fraction (XCS) and therefore higher extractables. Also important are the mechanical properties of the film, especially during sealing while the seal of the food packaging is still hot (i.e. so-called hot tack properties). Providing a balance between mechanical properties and sealing properties represents a challenge in which further progress may be achieved in terpolymer compositions for film applications.

[0004] Currently, many of these problems can be overcome by using multilayer films; however, these are disadvantageous for reasons of process economy and they are more difficult to recycle.Therefore, there is a need in the field of films for sealing, for light-weight, simple solutions.

[0005] In general, it is well known that standard nucleating agents / clarifiers (such as sorbitol derivatives and nonitol derivatives) may help improve the mechanical properties of the film; however, the same increased crystallization generally leads to higher sealing initiation temperatures, which is undesirable. It is therefore an object of the present invention to provide nucleated compositions in which improved mechanical properties can be obtained without sacrificing sealing properties and / or optical properties in order to obtain an improvement in mechanical properties. Summary of the invention

[0006] The present invention is based on the discovery that certain propylene / ethylene / 1-butene terpolymers in combination with certain alpha nucleating agents provide compositions that can form films that unexpectedly balance improved mechanical and optical properties without sacrificing sealing properties, and in particular have a wide temperature window within which good sealing properties can be achieved.

[0007] In a first aspect, the present invention relates to an α-nucleated single-phase propylene terpolymer composition (PC) comprising:

[0008] a) a propylene / ethylene / 1-butene random terpolymer (PP) having:

[0009] i) in the range of 0.75 to 4.0 mol% by quantitative 13 Ethylene content (C2) determined by C-NMR spectroscopy;

[0010] ii) in the range of 2.0 to 7.5 mol% by quantitative 13 1-Butene content (C4) determined by C-NMR spectroscopy;

[0011] and

[0012] iii) in the range of 0.1 to 1.5 mol% by quantitative 13 The content of 2,1-regio defects determined by C-NMR spectroscopy, and

[0013] b) one or more alpha nucleating agents (NU), wherein at least one of the one or more alpha nucleating agents is a particulate alpha nucleating agent,

[0014] wherein the total amount of the propylene / ethylene / 1-butene random terpolymer (PP) and the one or more α-nucleating agents (NU) amounts to at least 95 wt.-% of the total weight of the α-nucleated single-phase propylene terpolymer composition (PC),

[0015] The α-nucleated single-phase propylene terpolymer composition (PC) has each of the following properties:

[0016] i) a melt flow rate (MFR2) determined according to ISO 1133 at 230°C under a load of 2.16 kg in the range of 1.0 to 35 g / 10 min;

[0017] ii) a melting temperature in the range of 125 to 140°C as determined by DSC analysis; and

[0018] iii) Crystallization temperature determined by DSC analysis in the range of 95 to 115°C.

[0019] In a second aspect, the present invention relates to an α-nucleated single-phase propylene terpolymer composition (PC) having:

[0020] i) in the range of 0.75 to 4.0 mol% by quantitative 13 Ethylene content (C2) determined by C-NMR spectroscopy;

[0021] ii) in the range of 2.0 to 7.5 mol% by quantitative 13 1-Butene content (C4) determined by C-NMR spectroscopy;

[0022] iii) a melt flow rate (MFR2) measured according to ISO 1133 at 230°C under a load of 2.16 kg in the range of 1.0 to 35 g / 10 min;

[0023] iv) a melting temperature in the range of 125 to 140°C as determined by DSC analysis; and

[0024] v) a crystallization temperature determined by DSC analysis in the range of 95 to 115° C.,

[0025] The α-nucleated single-phase propylene terpolymer composition (PC) further has:

[0026] a) 1.5N hot tack seal process window measured on 50 μm blown film samples in the range of 15 to 25°C, or

[0027] b) 1.5N hot tack sealing process window measured on 50 μm cast film samples in the range of 20 to 30°C.

[0028] In a third aspect, the present invention relates to a process for producing an α-nucleated single-phase propylene terpolymer composition (PC) according to anyone of the first two aspects, comprising the following steps:

[0029] a) polymerizing propylene, ethylene and 1-butene comonomer units in the presence of a single site catalyst in a first polymerization reactor to produce a first polymerization mixture comprising a first random terpolymer fraction (PP1) and the single site catalyst, wherein the first polymerization reactor is preferably a slurry reactor, more preferably a loop reactor;

[0030] b) withdrawing the first polymerization mixture from the first polymerization reactor and optionally carrying out steps c1) to c3) before step d);

[0031] c1) transferring the first polymerization mixture to a second polymerization reactor, which is preferably a gas phase reactor;

[0032] c2) polymerizing propylene, ethylene and 1-butene comonomer units in the presence of said single site catalyst in said second polymerization reactor to produce a second polymerization mixture comprising a first random terpolymer fraction (PP1), a second random terpolymer fraction (PP2) and the single site catalyst;

[0033] c3) withdrawing the second polymerization mixture from the second polymerization reactor; and

[0034] d) compounding the first polymerization mixture with one or more alpha nucleating agents (NU), optionally with a visbreaking agent (V) and optionally with additional other additives to form an alpha-nucleated single-phase propylene terpolymer composition (PC) if steps c1) to c3) are absent or compounding the second polymerization mixture with one or more alpha nucleating agents (NU), optionally with a visbreaking agent (V) and optionally with additional other additives to form an alpha-nucleated single-phase propylene terpolymer composition (PC) if steps c1) to c3) are present.

[0035] In a last aspect, the present invention relates to an article, more preferably a film, comprising the α-nucleated single-phase propylene terpolymer composition (PC) according to anyone of the first two aspects in an amount of at least 75 wt%, more preferably at least 90 wt%, most preferably at least 95 wt%.

[0036] definition

[0037] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which the invention belongs. Although any methods and materials similar or equivalent to those described herein can be used in practice to test the present invention, preferred materials and methods are described herein. In describing and claiming the present invention, the following terms will be used in accordance with the definitions set forth below.

[0038] Unless expressly stated otherwise, the use of the terms "a," "an," etc. refers to one or more than one.

[0039] In the following, unless stated otherwise, the amounts are given in % by weight (wt %).

[0040] A propylene homopolymer is a polymer consisting essentially of propylene monomer units. Due to impurities, especially during commercial polymerization processes, the propylene homopolymer may contain up to 0.1 mol% comonomer units, preferably up to 0.05 mol% comonomer units, and most preferably up to 0.01 mol% comonomer units.

[0041] The random propylene copolymer is a copolymer of propylene monomer units and comonomer units, preferably selected from ethylene and C4-C8 alpha-olefins, wherein the comonomer units are randomly distributed along the polymer chain. The random propylene copolymer may contain comonomer units of one or more comonomers having different carbon atom weights.

[0042] The propylene random terpolymer is a random copolymer as described above comprising propylene and two different comonomer units, typically propylene, ethylene and a C4-C8 alpha-olefin.

[0043] Pseudo-terpolymers made from a mixture of two copolymers (e.g. a mixture of a propylene / ethylene copolymer and a propylene / 1-butene copolymer) are not included in the term "terpolymer" according to the present invention. Pseudo-terpolymers can be identified by coupled TREF-IR, coupled TREF-NMR or similar methods.

[0044] It is typical for single-phase propylene homopolymers and single-phase propylene random copolymers (including single-phase propylene random terpolymers) that only one glass transition temperature is present.

[0045] Bimodal polymers are polymers having a bimodal distribution of one or more properties.The bimodal random propylene terpolymer may generally be bimodal in comonomer content or bimodal in molecular weight (as can be seen by the melt flow rate of the first fraction and the final composition).

[0046] Particulate nucleating agents are a class of nucleating agents that have a very high melting temperature. During the processing of the polymer, they remain solid and do not melt and dissolve, but disperse into the polymer melt. This is different from soluble nucleating agents, which dissolve into the polymer melt during processing. DETAILED DESCRIPTION

[0047] Alpha-nucleated single-phase propylene terpolymer composition (PC)

[0048] In a first aspect, the present invention relates to an α-nucleated single-phase propylene terpolymer composition (PC) comprising:

[0049] a) a propylene / ethylene / 1-butene random terpolymer (PP) having:

[0050] i) in the range of 0.75 to 4.0 mol% by quantitative 13 Ethylene content (C2) determined by C-NMR spectroscopy;

[0051] ii) in the range of 2.0 to 7.5 mol% by quantitative 13 1-Butene content (C4) determined by C-NMR spectroscopy;

[0052] and

[0053] iii) in the range of 0.1 to 1.5 mol% by quantitative 13 The content of 2,1-regio defects determined by C-NMR spectroscopy, and

[0054] b) one or more alpha nucleating agents (NU), wherein at least one of the one or more alpha nucleating agents is a particulate alpha nucleating agent,

[0055] wherein the total amount of the propylene / ethylene / 1-butene random terpolymer (PP) and the one or more α-nucleating agents (NU) amounts to at least 95 wt.-% of the total weight of the α-nucleated single-phase propylene terpolymer composition (PC),

[0056] The α-nucleated single-phase propylene terpolymer composition (PC) has each of the following properties:

[0057] i) a melt flow rate (MFR2) determined according to ISO 1133 at 230°C under a load of 2.16 kg in the range of 1.0 to 35 g / 10 min;

[0058] ii) a melting temperature in the range of 125 to 140°C as determined by DSC analysis; and

[0059] iii) Crystallization temperature determined by DSC analysis in the range of 95 to 115°C.

[0060] In said first aspect, the α-nucleated single-phase propylene terpolymer composition preferably has:

[0061] a) 1.5N hot tack seal process window measured on 50 μm blown film samples in the range of 15 to 25°C, or

[0062] b) 1.5N hot tack sealing process window measured on 50 μm cast film samples in the range of 20 to 30°C.

[0063] In a second aspect, the present invention relates to an α-nucleated single-phase propylene terpolymer composition (PC) having:

[0064] i) in the range of 0.75 to 4.0 mol% by quantitative 13 Ethylene content (C2) determined by C-NMR spectroscopy;

[0065] ii) in the range of 2.0 to 7.5 mol% by quantitative 13 1-Butene content (C4) determined by C-NMR spectroscopy;

[0066] iii) a melt flow rate (MFR2) measured according to ISO 1133 at 230°C under a load of 2.16 kg in the range of 1.0 to 35 g / 10 min;

[0067] iv) a melting temperature in the range of 125 to 140°C as determined by DSC analysis; and

[0068] v) a crystallization temperature determined by DSC analysis in the range of 95 to 115° C.,

[0069] The α-nucleated single-phase propylene terpolymer composition (PC) further has:

[0070] a) 1.5N hot tack seal process window measured on 50 μm blown film samples in the range of 15 to 25°C, or

[0071] b) 1.5N hot tack sealing process window measured on 50 μm cast film samples in the range of 20 to 30°C.

[0072] In the second aspect, the α-nucleated single-phase propylene terpolymer composition (PC) preferably comprises:

[0073] a) a propylene / ethylene / 1-butene random terpolymer (PP) having:

[0074] i) in the range of 0.75 to 4.0 mol% by quantitative 13 Ethylene content (C2) determined by C-NMR spectroscopy;

[0075] ii) in the range of 2.0 to 7.5 mol% by quantitative 13 1-Butene content (C4) determined by C-NMR spectroscopy;

[0076] and

[0077] iii) in the range of 0.1 to 1.5 mol% by quantitative 13 The content of 2,1-regio defects determined by C-NMR spectroscopy, and

[0078] b) one or more alpha nucleating agents (NU), wherein at least one of the one or more alpha nucleating agents is a particulate alpha nucleating agent,

[0079] wherein the total amount of the propylene / ethylene / 1-butene random terpolymer (PP) and the one or more α-nucleating agents (NU) amounts to at least 95 wt.-% based on the total weight of the α-nucleated single-phase propylene terpolymer composition (PC).

[0080] Unless explicitly stated otherwise, all further alternative and preferred embodiments apply equally to the α-nucleated single-phase propylene terpolymer composition (PC) of the first and second aspects.

[0081] The α-nucleated single-phase propylene terpolymer composition (PC) has a melt flow rate (MFR2) determined according to ISO 1133 at 230 °C under a load of 2.16 kg in the range of 1.0 to 35 g / 10 min, more preferably in the range of 3.0 to 33 g / 10 min, most preferably in the range of 5.0 to 32 g / 10 min.

[0082] The α-nucleated single-phase propylene terpolymer composition (PC) according to this invention may be visbroken or non-visbroken.

[0083] As is well known to those skilled in the art, the visbreaking process involves treating a precursor polymer with a visbreaking agent (i.e., a free radical generator). The polymer chains of the precursor polymer may undergo a β-fracture process and / or crosslinking, although in the absence of a specific crosslinking agent, which is usually a small molecule with multiple unsaturated sites (e.g., a di- or tri-olefin), the β-fracture process tends to dominate. The effect of visbreaking is that the high molecular weight fraction in the molecular weight distribution is cracked to form polymer chains of lower molecular weight. Since these high molecular weight fractions contribute disproportionately to the MFR2 of the entire polymer, visbreaking is used to increase the MFR2 of the polymer.

[0084] As will be apparent to those skilled in the art, it may be determined whether a polymer has been visbroken not only by evaluating the shape of the resulting molecular weight distribution curve, but also by the presence of decomposition products of the visbreaking agent (eg peroxide decomposition products).

[0085] Due to the visbreaking procedure, some other properties of the polymer may be slightly changed, for example a small change in the XCS content can be expected; however, the main effects are rheological / molecular weight parameters such as melt flow rate. In principle, properties such as comonomer content should not be affected by the visbreaking process; however, due to measurement errors, small differences may be observed (e.g. the presence of cross-linking substances may complicate the calculations for determining the comonomer content). Such differences are almost negligible in practice.

[0086] In a first embodiment the α-nucleated single-phase propylene terpolymer composition (PC) according to this invention is not visbroken.

[0087] In the non-visbroken embodiment the α-nucleated single-phase propylene terpolymer composition (PC) has a melt flow rate (MFR2) measured according to ISO 1133 at 230 °C under a load of 2.16 kg in the range of 1.0 to 10.0 g / 10 min, more preferably in the range of 3.0 to 9.0 g / 10 min, most preferably in the range of 5.0 to 8.0 g / 10 min.

[0088] In a second embodiment, the propylene / ethylene / 1-butene random terpolymer (PP) has been formed by visbreaking the precursor propylene / ethylene / 1-butene random terpolymer (PP') using a visbreaking agent, more preferably a peroxide radical generator.

[0089] In this visbroken embodiment the α-nucleated single-phase propylene terpolymer composition (PC) has a melt flow rate (MFR2) measured according to ISO 1133 at 230 °C under a load of 2.16 kg in the range of 20 to 35 g / 10 min, more preferably in the range of 25 to 33 g / 10 min, most preferably in the range of 28 to 32 g / 10 min.

[0090] The precursor propylene / ethylene / 1-butene random terpolymer (PP') preferably has a melt flow rate (MFR2) measured at 230°C under a load of 2.16 kg according to ISO 1133 in the range of 1.0 to 10.0 g / 10 min, more preferably in the range of 3.0 to 9.0 g / 10 min, most preferably in the range of 5.0 to 8.0 g / 10 min.

[0091] In all other respects (except melt flow rate), the alternative ranges and preferred embodiments given above and below for the propylene / ethylene / 1-butene random terpolymer (PP) apply mutatis mutandis to the precursor propylene / ethylene / 1-butene random terpolymer (PP').

[0092] The α-nucleated single-phase propylene terpolymer composition (PC) of the first aspect preferably has a content of propylene oxide in the range of 0.75 to 4.0 mol%, more preferably in the range of 1.2 to 3.0 mol%, most preferably in the range of 1.5 to 2.5 mol%. 13 Ethylene content (C2) determined by C-NMR spectroscopy.

[0093] The α-nucleated single-phase propylene terpolymer composition (PC) of the first aspect preferably has a content of 2.0 to 7.5 mol%, more preferably 2.5 to 6.0 mol%, most preferably 3.0 to 5.0 mol% of the terpolymer consisting of 13 1-Butene content (C4) determined by C-NMR spectroscopy.

[0094] The α-nucleated single-phase propylene terpolymer composition (PC) of the second aspect has a content of 0.75 to 4.0 mol%, more preferably 1.2 to 3.0 mol%, most preferably 1.5 to 2.5 mol% of the propylene terpolymer. 13 Ethylene content (C2) determined by C-NMR spectroscopy.

[0095] The α-nucleated single-phase propylene terpolymer composition (PC) of the second aspect has a content of 2.0 to 7.5 mol%, more preferably 2.5 to 6.0 mol%, most preferably 3.0 to 5.0 mol% of the propylene terpolymer consisting of a quantitative 131-Butene content (C4) determined by C-NMR spectroscopy.

[0096] The α-nucleated single-phase propylene terpolymer composition (PC) has a melting temperature determined according to DSC analysis in the range of 125 to 140 °C, more preferably in the range of 130 to 139 °C, most preferably in the range of 135 to 138 °C.

[0097] It is preferred that the melting temperature has an associated enthalpy of melting determined according to DSC analysis in the range of 50 to 80 J / g, more preferably in the range of 60 to 77 J / g, most preferably in the range of 70 to 75 J / g.

[0098] It is further preferred that the melting temperature is 1.0 to 6.0 °C higher, more preferably 2.0 to 5.0 °C higher, most preferably 3.0 to 4.0 °C higher than a similar non-nucleated single-phase propylene terpolymer composition.

[0099] The α-nucleated single-phase propylene terpolymer composition (PC) has a crystallization temperature determined according to DSC analysis in the range of 95 to 115 °C, more preferably in the range of 100 to 112 °C, most preferably in the range of 105 to 110 °C.

[0100] It is further preferred that the crystallization temperature is 5.0 to 15.0 °C higher, more preferably 8.0 to 14.0 °C higher, most preferably 10.0 to 3.0 °C higher than a similar non-nucleated single-phase propylene terpolymer composition.

[0101] It is preferred that the crystallization temperature has an associated crystallization enthalpy determined according to DSC analysis in the range of 50 to 80 J / g, more preferably in the range of 60 to 77 J / g, most preferably in the range of 70 to 75 J / g.

[0102] Since the α-nucleated single-phase propylene terpolymer composition (PC) is not a multiphase system comprising an elastomeric rubber layer, the α-nucleated propylene terpolymer composition (PC) preferably does not have a glass transition temperature below -30°C, more preferably does not have a glass transition temperature below -25°C, most preferably does not have a glass transition temperature below -20°C.

[0103] It is preferred that the α-nucleated single-phase propylene terpolymer composition (PC) has a clarity value determined according to ASTM D1003 on a 50 μm cast film sample in the range of 98.0 to 100 %, more preferably in the range of 99.0 to 100 %, most preferably in the range of 99.5 to 100 %, and / or

[0104] Clarity values ​​in the range of 98.0 to 100%, more preferably in the range of 99.0 to 100%, most preferably in the range of 99.5 to 100% as measured according to ASTM D1003 on 50 μm blown film specimens.

[0105] It is preferred that the α-nucleated single-phase propylene terpolymer composition (PC) has a haze value measured on a 50 μm cast film sample according to ASTM D1003 in the range of 0.0 to 1.0%, more preferably in the range of 0.0 to 0.7%, most preferably in the range of 0.0 to 0.5%, and / or

[0106] Haze values ​​in the range of 0.0 to 4.0%, more preferably in the range of 0.0 to 3.0%, most preferably in the range of 0.0 to 2.5% measured according to ASTM D1003 on 50 μm blown film samples.

[0107] It is preferred that the α-nucleated single-phase propylene terpolymer composition (PC) has a seal initiation temperature (SIT) measured on a 50 μm cast film sample in the range of 100 to 120 °C, more preferably in the range of 102 to 115 °C, most preferably in the range of 103 to 110 °C, and / or

[0108] The seal initiation temperature (SIT) measured on a 50 μm blown film sample is in the range of 110 to 125°C, more preferably in the range of 112 to 120°C, most preferably in the range of 113 to 117°C.

[0109] It is preferred that the α-nucleated single-phase propylene terpolymer composition (PC) has a seal end temperature (SET) measured on 50 μm cast film samples in the range of 115 to 130 °C, more preferably in the range of 120 to 128 °C, most preferably in the range of 123 to 127 °C.

[0110] It is preferred that the α-nucleated single-phase propylene terpolymer composition (PC) has a difference between the seal end temperature (SET) and the seal initiation temperature (SIT), both measured on a 50 μm cast film sample, in the range of 10 to 25 °C, more preferably in the range of 13 to 22 °C, most preferably in the range of 15 to 20 °C.

[0111] It is preferred that the α-nucleated single-phase propylene terpolymer composition (PC) has a difference between the melting temperature determined according to DSC analysis and the seal initiation temperature (SIT) determined on a 50 μm cast film sample in the range of 25 to 40 °C, more preferably in the range of 28 to 37 °C, most preferably in the range of 30 to 34 °C, and / or

[0112] The difference between the melting temperature determined according to DSC analysis and the seal initiation temperature (SIT) determined on a 50 μm blown film sample of the α-nucleated single-phase propylene terpolymer composition (PC) is in the range of 15 to 30 °C, more preferably in the range of 18 to 27 °C, most preferably in the range of 20 to 24 °C.

[0113] It is preferred that the α-nucleated single-phase propylene terpolymer composition (PC) has a maximum sealing force measured on a 50 μm cast film sample in the range of 10 to 25 N, more preferably in the range of 13 to 22 N, most preferably in the range of 15 to 20 N, and / or

[0114] The maximum sealing force measured on a 50 μm blown film sample is in the range of 15 to 30 N, more preferably in the range of 18 to 27 N, most preferably in the range of 20 to 25 N.

[0115] It is preferred that the α-nucleated single-phase propylene terpolymer composition (PC) has a hot tack measured according to ASTM F1921-12-method B on 50 μm cast film samples in the range of 2.0 to 5.0 N, more preferably in the range of 2.5 to 4.5 N, most preferably in the range of 3.0 to 4.0 N, and / or

[0116] Hot tack measured according to ASTM F1921 -12 - Method B on 50 μm blown film samples in the range of 2.0 to 5.0 N, more preferably in the range of 2.5 to 4.5 N, most preferably in the range of 3.0 to 4.0 N.

[0117] It is preferred that the α-nucleated single-phase propylene terpolymer composition (PC) has a hot stick temperature measured on a 50 μm cast film sample in the range of 95 to 115 °C, more preferably in the range of 100 to 110 °C, most preferably in the range of 104 to 106 °C, and / or

[0118] Hot stick temperature measured on a 50 μm blown film sample in the range of 100 to 115°C, more preferably in the range of 105 to 113°C, most preferably in the range of 108 to 111°C.

[0119] It is preferred that the α-nucleated single-phase propylene terpolymer composition (PC) has a 1.5 N hot tack sealing process window measured on a 50 μm cast film sample in the range of 20 to 30 °C, more preferably in the range of 22 to 28 °C, most preferably in the range of 23 to 27 °C, and / or

[0120] The 1.5 N hot tack seal process window measured on a 50 μm blown film sample is in the range of 15 to 25°C, more preferably in the range of 17 to 23°C, most preferably in the range of 18 to 22°C.

[0121] It is preferred that the α-nucleated single-phase propylene terpolymer composition (PC) has a tensile storage modulus (E') measured on a 50 μm cast film sample in the range of 600 to 1500 MPa, more preferably in the range of 700 to 1200 MPa, most preferably in the range of 750 to 1000 MPa, and / or

[0122] Tensile storage modulus (E') measured on 50 μm blown film samples in the range of 1000 to 1700 MPa, more preferably in the range of 1200 to 1600 MPa, most preferably in the range of 1300 to 1500 MPa.

[0123] It is preferred that the α-nucleated single-phase propylene terpolymer composition (PC) has a dart impact strength measured according to ASTM D1709-A on a 50 μm cast film sample in the range of 350 to 550 g, more preferably in the range of 380 to 500 g, most preferably in the range of 410 to 450 g, and / or

[0124] Dart impact strength measured according to ASTM D1709-A on 50 μm blown film samples in the range of 40 to 60 g, more preferably in the range of 45 to 57 g, most preferably in the range of 50 to 55 g.

[0125] It is preferred that the α-nucleated single-phase propylene terpolymer composition (PC) has a gloss at 60° measured on 50 μm blown film samples in machine direction according to ISO 2813 in the range of 120 to 170 GU, more preferably in the range of 130 to 160 GU, most preferably in the range of 135 to 150 GU.

[0126] It is preferred that the α-nucleated single-phase propylene terpolymer composition (PC) has a gloss at 60° measured on 50 μm blown film samples in transverse direction according to ISO 2813 in the range of 120 to 170 GU, more preferably in the range of 130 to 160 GU, most preferably in the range of 135 to 150 GU.

[0127] In a first aspect, the α-nucleated single-phase propylene terpolymer composition (PC) comprises a propylene / ethylene / 1-butene random terpolymer (PP) and one or more α-nucleating agents, wherein at least one of the one or more α-nucleating agents is a particulate α-nucleating agent.

[0128] In the second aspect, the α-nucleated single-phase propylene terpolymer composition (PC) preferably comprises a propylene / ethylene / 1-butene random terpolymer (PP) and one or more α-nucleating agents, wherein at least one of the one or more α-nucleating agents is a particulate α-nucleating agent.

[0129] In both aspects it is preferred that the α-nucleated single-phase propylene terpolymer composition (PC) comprises the propylene / ethylene / 1-butene random terpolymer (PP) in an amount in the range of 90.0 to 99.99 wt.-%, more preferably in the range of 95.0 to 99.9 wt.-%, most preferably in the range of 99.0 to 99.8 wt.-%.

[0130] In both aspects it is preferred that the α-nucleated single-phase propylene terpolymer composition (PC) comprises one or more α-nucleating agents (NU) in a total amount of 0.01 to 1.00 wt-%, more preferably in the range of 0.05 to 0.50 wt-%, most preferably in the range of 0.08 to 0.30 wt-%.

[0131] In addition to the propylene / ethylene / 1-butene random terpolymer (PP) and one or more α-nucleating agents (NU), the α-nucleated single-phase propylene terpolymer composition (PC) may contain other additives known in the art; however, the remaining portion in the α-nucleated single-phase propylene terpolymer composition (PC) must not exceed 5.0 wt%, such as not more than 3.0 wt%. For example, the α-nucleated single-phase propylene terpolymer composition (PC) may additionally contain a small amount of additives (A) selected from the group consisting of antioxidants, stabilizers, fillers, colorants, nucleating agents and antistatic agents. Typically, they can be incorporated during compounding of the α-nucleated single-phase propylene terpolymer composition (PC).

[0132] It is preferred that the α-nucleated single-phase propylene terpolymer composition (PC) contains no β-nucleating agent.

[0133] In case the α-nucleated single-phase propylene terpolymer composition (PC) comprises an α-nucleating agent other than a particulate α-nucleating agent, it is preferred that any additional α-nucleating agent is preferably selected from the group consisting of

[0134] (i) salts of mono- and polycarboxylic acids, for example sodium benzoate or aluminium tert-butylbenzoate, and

[0135] (ii) salts of diesters of phosphoric acid, for example sodium 2,2'-methylenebis(4,6-di-tert-butylphenyl)phosphate or hydroxybis[2,2'-methylene-bis(4,6-di-tert-butylphenyl)phosphate]aluminum, and

[0136] (iii) vinyl cycloalkane polymers and vinyl alkane polymers (as discussed in more detail below), and

[0137] (iv) mixtures thereof.

[0138] Such additives are generally commercially available and are described, for example, in “Plastic Additives Handbook” by Hans Zweifel, pages 871 to 873, 5th edition, 2001.

[0139] It is to be understood that the amount of additive (A) given relative to the total weight of the α-nucleated single-phase propylene terpolymer composition (PC) includes any carrier polymer, i.e. a masterbatch carrier polymer, used to introduce the additive into the α-nucleated single-phase propylene terpolymer composition (PC). An example of such a carrier polymer is a polypropylene homopolymer in the form of a powder.

[0140] In a specific embodiment the α-nucleated single-phase propylene terpolymer composition (PC) consists of a propylene / ethylene / 1-butene random terpolymer (PP), one or more α-nucleating agents (NU) and optionally additives (A).

[0141] Propylene / ethylene / 1-butene random terpolymer (PP)

[0142] The propylene / ethylene / 1-butene random terpolymer (PP) preferably has a melt flow rate (MFR2) measured at 230°C under a load of 2.16 kg according to ISO 1133 in the range of 1.0 to 10.0 g / 10 min, more preferably in the range of 3.0 to 9.0 g / 10 min, most preferably in the range of 5.0 to 8.0 g / 10 min.

[0143] The propylene / ethylene / 1-butene random terpolymer (PP) has a quantitative 13 Ethylene content (C2) determined by C-NMR spectroscopy.

[0144] The propylene / ethylene / 1-butene random terpolymer (PP) has a quantitative 13 1-Butene content (C4) determined by C-NMR spectroscopy.

[0145] The propylene / ethylene / 1-butene random terpolymer (PP) has a quantitative 13 The content of 2,1-regio defects was determined by C-NMR spectroscopy.

[0146] The presence of 2,1-regio defects in a propylene / ethylene / 1-butene random terpolymer (PP) generally indicates that the propylene / ethylene / 1-butene random terpolymer (PP) has been polymerized in the presence of a single site catalyst (SSC).

[0147] Thus, it is preferred that the propylene / ethylene / 1-butene random terpolymer (PP) has been polymerized in the presence of a single site catalyst (SSC), more preferably a metallocene catalyst. It is particularly preferred that the propylene / ethylene / 1-butene random terpolymer (PP) has been polymerized according to the process of the third embodiment as described below.

[0148] The content of 2,1-regio defects may depend on the amount of comonomer, with higher amounts of comonomer generally being associated with lower contents of 2,1-regio defects.

[0149] The content of 2,1-regio defects may also depend on the polymerization temperature, with higher temperatures generally associated with lower contents of 2,1-regio defects.

[0150] The propylene / ethylene / 1-butene random terpolymer (PP) preferably has a xylene cold soluble content (XCS) determined according to ISO 16152 in the range of 1.00 to 4.00 wt.-%, more preferably in the range of 1.5 to 3.5 wt.-%, most preferably in the range of 1.80 to 3.00 wt.-%.

[0151] The propylene / ethylene / 1-butene random terpolymer (PP) preferably has a melting temperature determined according to DSC analysis in the range of 125 to 140°C, more preferably in the range of 128 to 137°C, most preferably in the range of 131 to 135°C.

[0152] It is preferred that the melting temperature has an associated enthalpy of melting determined according to DSC analysis in the range of 50 to 80 J / g, more preferably in the range of 60 to 77 J / g, most preferably in the range of 68 to 73 J / g.

[0153] The propylene / ethylene / 1-butene random terpolymer (PP) preferably has a crystallization temperature determined according to DSC analysis in the range of 85 to 100°C, more preferably in the range of 90 to 98°C, most preferably in the range of 94 to 97°C.

[0154] It is further preferred that the crystallization temperature is 5.0 to 15.0 °C higher, more preferably 8.0 to 14.0 °C higher, most preferably 10.0 to 3.0 °C higher than a similar non-nucleated single-phase propylene terpolymer composition.

[0155] The propylene / ethylene / 1-butene random terpolymer (PP) can be unimodal or multimodal, like bimodal.

[0156] As is well known to those skilled in the art, the modality of a polymer composition can be defined with respect to a number of properties, the most common of which is multimodality, such as bimodality, with respect to melt flow rate or comonomer content.

[0157] Particularly preferred are propylene / ethylene / 1-butene random terpolymers (PP) which are bimodal with respect to the melt flow rate, with respect to the ethylene content or with respect to the 1-butene content.

[0158] A bimodal polymer can be produced by blending two unimodal polymers or by utilizing a multi-reactor polymerization process wherein a first polymer fraction is polymerized in a first polymerization reactor, wherein the first polymer fraction is transferred to a second polymerization reactor, wherein a second polymer fraction that differs from the first polymer fraction in one or more properties is polymerized under different conditions, thereby forming a bimodal polymer.

[0159] Accordingly, it is preferred that the propylene / ethylene / 1-butene random terpolymer (PP) comprises a first random terpolymer fraction (PP1) and a second terpolymer fraction (PP2) as described below.

[0160] Particularly preferred are propylene / ethylene / 1-butene random terpolymers (PP) comprising:

[0161] a) 40 to 80 wt.-% of a first random terpolymer fraction (PP1) relative to the total weight of the propylene / ethylene / 1-butene random terpolymer (PP), the first random terpolymer fraction (PP1) having in the range of 0.75 to 4.0 mol-% of a quantitative 13 The ethylene content (C2) determined by C-NMR spectroscopy and the ethylene content (C2) in the range of 1.0 to 5.0 mol % by quantitative 13 1-Butene content (C4) determined by C-NMR spectroscopy; and

[0162] b) 20 to 60 wt.-% of a second random terpolymer fraction (PP2) relative to the total weight of the propylene / ethylene / 1-butene random terpolymer (PP), the second random terpolymer fraction (PP2) having in the range of 0.75 to 4.0 mol-% of a quantitative 13 The ethylene content (C2) determined by C-NMR spectroscopy and the ethylene content (C2) in the range of 3.0 to 10.0 mol % by quantitative 13 1-Butene content (C4) determined by C-NMR spectroscopy,

[0163] Wherein the combined first random terpolymer fraction (PP1) and the second random terpolymer fraction (PP2) constitute at least 95 wt.-% of the total weight of the propylene / ethylene / 1-butene random terpolymer (PP).

[0164] First random terpolymer fraction (PP1)

[0165] The first random terpolymer fraction (PP1) is a terpolymer of propylene, ethylene and 1-butene.

[0166] The first random terpolymer fraction (PP1) preferably has a content of 0.75 to 4.0 mol %, more preferably 1.5 to 3.5 mol %, most preferably 2.0 to 3.0 mol % of the quantitative 13 Ethylene content (C2) determined by C-NMR spectroscopy.

[0167] The first random terpolymer fraction (PP1) preferably has a content of 1.0 to 5.0 mol %, more preferably 1.5 to 4.0 mol %, most preferably 2.0 to 3.0 mol % of the quantitative 13 1-Butene content (C4) determined by C-NMR spectroscopy.

[0168] The first random terpolymer fraction (PP1) preferably has a melt flow rate (MFR2) measured at 230°C under a load of 2.16 kg according to ISO 1133 in the range of 1.0 to 10 g / 10 min, more preferably in the range of 3.0 to 8.0 g / 10 min, most preferably in the range of 5.0 to 7.0 g / 10 min.

[0169] Second random terpolymer fraction (PP2)

[0170] The second random terpolymer fraction (PP2) is a terpolymer of propylene, ethylene and 1-butene.

[0171] The second random terpolymer fraction (PP2) has a quantitative 13 Ethylene content (C2) determined by C-NMR spectroscopy.

[0172] The second random terpolymer fraction (PP2) has a quantitative 13 1-Butene content (C4) determined by C-NMR spectroscopy.

[0173] The second random terpolymer fraction (PP2) preferably has a melt flow rate (MFR2) measured at 230°C under a load of 2.16 kg according to ISO 1133 in the range of 1.0 to 20.0 g / 10 min, more preferably in the range of 4.0 to 17.0 g / 10 min, most preferably in the range of 7.0 to 14.0 g / 10 min.

[0174] Bimodal propylene / ethylene / 1-butene random terpolymer

[0175] The bimodal propylene / ethylene / 1-butene random terpolymer comprises 40 to 80 wt.-% of a first random terpolymer fraction (PP1), relative to the total weight of the bimodal propylene / ethylene / 1-butene random terpolymer, and 20 to 60 wt.-% of a second random terpolymer fraction (PP2), relative to the total weight of the bimodal propylene / ethylene / 1-butene random terpolymer.

[0176] More preferably, the bimodal propylene / ethylene / 1-butene random terpolymer comprises 50 to 75 wt.-% of the first random terpolymer fraction (PP1), relative to the total weight of the bimodal propylene / ethylene / 1-butene random terpolymer composition, and 25 to 50 wt.-% of the second random terpolymer fraction (PP2), relative to the total weight of the bimodal propylene / ethylene / 1-butene random terpolymer.

[0177] It is especially preferred that the bimodal propylene / ethylene / 1-butene random terpolymer comprises 55 to 70 wt.-% of the first random terpolymer fraction (PP1), relative to the total weight of the bimodal propylene / ethylene / 1-butene random terpolymer, and 30 to 45 wt.-% of the second random terpolymer fraction (PP2), relative to the total weight of the bimodal propylene / ethylene / 1-butene random terpolymer.

[0178] The combined first random terpolymer fraction (PP1) and the second random terpolymer fraction (PP2) constitute at least 95 wt.-% of the total weight of the bimodal propylene / ethylene / 1-butene random terpolymer (PP).

[0179] As mentioned previously, the bimodal propylene / ethylene / 1-butene random terpolymer may be bimodal with respect to the molecular weight (as indicated by the melt flow rate value). Accordingly, it is preferred that the ratio of the melt flow rate (MFR2) of the bimodal propylene / ethylene / 1-butene random terpolymer (PP) to the melt flow rate (MFR2) of the first random terpolymer fraction (PP1) ([MFR(PP)] / [MFR(PP1)]) is in the range of 0.50 to 1.50, more preferably in the range of 0.80 to 1.30, most preferably in the range of 1.00 to 1.20, both melt flow rates being determined according to ISO 1133 at 230°C under a load of 2.16 kg and expressed in g / 10 min.

[0180] The bimodal propylene / ethylene / 1-butene random terpolymer may additionally or alternatively be bimodal with respect to the comonomer content, i.e. bimodal with respect to the ethylene content, the 1-butene content or both. Thus, the ethylene content of the first random terpolymer fraction C2(PP1) may differ from the ethylene content of the second random terpolymer fraction C2(PP2) and / or the 1-butene content of the first random terpolymer fraction C4(PP1) may differ from the 1-butene content of the second random terpolymer fraction C4(PP2).

[0181] As mentioned previously, the bimodal propylene / ethylene / 1-butene random terpolymer may be bimodal with respect to the ethylene content. Thus, it is preferred that the ratio of the ethylene content of the bimodal propylene / ethylene / 1-butene random terpolymer (PP) to the ethylene content of the first random terpolymer fraction (PP1) ([C2(PP)] / [C2(PP1)]) is in the range of 0.70 to 1.30, more preferably in the range of 0.80 to 1.20, most preferably in the range of 0.90 to 1.10, both ethylene contents being determined by quantitative 13 The amounts were determined by C-NMR spectroscopy and are expressed in mol %.

[0182] As mentioned previously, the bimodal propylene / ethylene / 1-butene random terpolymer may be bimodal with respect to the 1-butene content. Thus, it is preferred that the ratio of the 1-butene content of the bimodal propylene / ethylene / 1-butene random terpolymer to the 1-butene content of the first random terpolymer fraction (PP1) ([C4(PP)] / [C4(PP1)]) is in the range of 1.00 to 2.00, more preferably in the range of 1.20 to 1.70, most preferably in the range of 1.30 to 1.50, both 1-butene contents being determined by quantitative 13 The amounts were determined by C-NMR spectroscopy and are expressed in mol %.

[0183] One or more alpha nucleating agents (NU)

[0184] At least one of the one or more alpha nucleating agents is a particulate alpha nucleating agent.

[0185] Preferably, at least one of the one or more alpha nucleating agents (NU) is a particulate alpha nucleating agent comprising a compound having a phosphate moiety.

[0186] Preferably, at least one of the one or more alpha nucleating agents (NU) is a particulate alpha nucleating agent comprising a granular alpha nucleating agent having the structure [(Ar 1 O)(Ar 2 O)(O=)PO] n A compound of X, wherein

[0187] Ar 1 and Ar 2 Each is independently selected from phenyl groups substituted by one or more C1 to C6 straight or branched alkyl groups, wherein Ar 1 and Ar 2 It can also be connected by a direct single bond, O or a C1 to C6 alkylene group

[0188] n is 1 or 2, wherein if n=1, X is selected from the group consisting of Li, Na, K and Al(OH)2, and more preferably selected from the group consisting of Li, Na and K, and if n=2, X is selected from the group consisting of Mg, Ca and Al(OH), and more preferably selected from the group consisting of Mg and Ca.

[0189] More preferably, at least one of the one or more alpha nucleating agents (NU) is a particulate alpha nucleating agent comprising a compound selected from the group consisting of sodium di(4-tert-butylphenyl)phosphate, sodium 2,2'-methylene-bis-(4,6-di-tert-butylphenyl)phosphate, lithium 2,2'-methylene-bis-(4,6-di-tert-butylphenyl)phosphate and hydroxybis[2,2'-methylene-bis(4,6-di-tert-butylphenyl)phosphate]aluminum, still more preferably selected from the group consisting of sodium di(4-tert-butylphenyl)phosphate, sodium 2,2'-methylene-bis-(4,6-di-tert-butylphenyl)phosphate, lithium 2,2'-methylene-bis-(4,6-di-tert-butylphenyl)phosphate.

[0190] Most preferably, at least one of the one or more alpha nucleating agents (NU) comprises lithium 2,2'-methylene-bis-(4,6-di-tert-butylphenyl)phosphate.

[0191] As will be appreciated by those skilled in the art, such particulate alpha nucleating agents may be present as a single compound or as a particulate blend. One such particulate blend containing lithium 2,2'-methylene-bis-(4,6-di-tert-butylphenyl)phosphate as a major component is ADK STAB NA-71 commercially available from Adeka Corporation.

[0192] In an alternative embodiment, at least one of the one or more alpha nucleating agents (NU) is a particulate alpha nucleating agent comprising a dicarboxylic acid derivative.

[0193] It is preferred that at least one of the one or more alpha nucleating agents (NU) is a particulate alpha nucleating agent comprising a compound having a structure according to formula (I)

[0194]

[0195] Where R 1 , R 2 , R 3 , R 4 , R 5 , R 6 , R 7 , R 8 , R 9 and R 10 are each independently selected from hydrogen and C1 to C 10 Hydrocarbyl groups;

[0196] The R on the adjacent carbon atom 3 To R 10 Two of may be fused to form a cyclic hydrocarbon structure;

[0197] The R on non-adjacent carbon atoms 3 To R 10 Two of the may be fused to form a bicyclic hydrocarbon structure;

[0198] M is a group selected from the group consisting of sodium, potassium, calcium, strontium, lithium, zinc, magnesium and monobasic aluminium;

[0199] n is 1 or 2;

[0200] z is 1 or 2;

[0201] The sum of n+z is 3.

[0202] More preferably, R 1 , R 2 , R 3 , R 4 , R 5 , R 6 , R7 , R 8 , R 9 and R 10 Each is independently selected from hydrogen and a C1 to C4 alkyl group, even more preferably selected from hydrogen, methyl or ethyl. In a particularly preferred embodiment, R 1 , R 2 , R 3 , R 4 , R 5 , R 6 , R 7 , R 8 , R 9 and R 10 Each is hydrogen.

[0203] M is preferably sodium or calcium.

[0204] It is particularly preferred that at least one of the one or more alpha nucleating agents (NU) is a particulate alpha nucleating agent comprising a compound selected from bicyclo(2.2.1)heptane-2,3-dicarboxylic acid, disodium salt and calcium 1,2-cyclohexanedicarboxylate, most preferably calcium (1R,2S)-cyclohexanedicarboxylate.

[0205] As will be appreciated by those skilled in the art, such particulate alpha nucleating agents may be present as a single compound or in a particulate blend. One such particulate blend containing calcium (1R,2S)-cyclohexanedicarboxylate as a major component is Hyperform HPN 20E commercially available from Milliken Chemical.

[0206] method

[0207] The present invention further relates to a process for producing an α-nucleated single-phase propylene terpolymer composition (PC) according to any of the first two aspects, comprising the following steps:

[0208] a) polymerizing propylene, ethylene and 1-butene comonomer units in the presence of a single site catalyst in a first polymerization reactor to produce a first polymerization mixture comprising a first random terpolymer fraction (PP1) and the single site catalyst, wherein the first polymerization reactor is preferably a slurry reactor, more preferably a loop reactor;

[0209] b) withdrawing the first polymerization mixture from the first polymerization reactor and optionally carrying out steps c1) to c3) before step d);

[0210] c1) transferring the first polymerization mixture to a second polymerization reactor, which is preferably a gas phase reactor;

[0211] c2) polymerizing propylene, ethylene and 1-butene comonomer units in the presence of said single site catalyst in said second polymerization reactor to produce a second polymerization mixture comprising a first random terpolymer fraction (PP1), a second random terpolymer fraction (PP2) and the single site catalyst;

[0212] c3) withdrawing the second polymerization mixture from the second polymerization reactor; and

[0213] d) compounding the first polymerization mixture with one or more alpha nucleating agents (NU), optionally with a visbreaking agent (V) and optionally with additional other additives to form an alpha-nucleated single-phase propylene terpolymer composition (PC) if steps c1) to c3) are absent or compounding the second polymerization mixture with one or more alpha nucleating agents (NU), optionally with a visbreaking agent (V) and optionally with additional other additives to form an alpha-nucleated single-phase propylene terpolymer composition (PC) if steps c1) to c3) are present.

[0214] As discussed above, the propylene / ethylene / 1-butene random terpolymer (PP) can be unimodal or bimodal. If the propylene / ethylene / 1-butene random terpolymer (PP) is unimodal, steps c1) to c3) are not present. If the propylene / ethylene / 1-butene random terpolymer (PP) is bimodal, steps c1) to c3) are present.

[0215] It is preferred that the operating temperature in the first polymerization reactor (R1 ) is in the range of 62 to 85 °C, more preferably in the range of 65 to 82 °C, still more preferably in the range of 67 to 80 °C.

[0216] Alternatively or additionally with respect to the previous paragraph, it is preferred that the operating temperature in the second polymerization reactor (R2) is in the range of 75 to 95 °C, more preferably in the range of 78 to 92 °C.

[0217] Typically, the pressure in the first polymerization reactor (R1), preferably the loop reactor (LR), is in the range of 20 to 80 bar, preferably in the range of 30 to 70 bar, such as in the range of 35 to 65 bar, and the pressure in the second polymerization reactor (R2), i.e. the gas phase reactor (GPR), is in the range of 5 to 50 bar, preferably in the range of 15 to 40 bar.

[0218] Preferably, hydrogen is added to each polymerization reactor to control the molecular weight, ie the melt flow rate MFR2.

[0219] In addition to the (main) polymerization of the propylene random terpolymer in the two polymerization reactors (R1 and R2), the preparation of the propylene random terpolymer may also comprise a prepolymerization in a prepolymerization reactor (PR) upstream of the first polymerization reactor (R1) prior to the (main) polymerization.

[0220] In the prepolymerization reactor (PR), polypropylene (pre-PP) is produced. The prepolymerization is carried out in the presence of a single site catalyst (SSC). According to this embodiment, the single site catalyst is introduced into the prepolymerization step. However, this does not exclude the option of adding, for example, a further cocatalyst at a subsequent stage, in the polymerization process, for example in the first reactor (R1). In one embodiment, if prepolymerization is applied, all components of the single site catalyst are added only to the prepolymerization reactor (PR).

[0221] The prepolymerization reaction is usually carried out at a temperature of 0 to 60°C, preferably 15 to 50°C, more preferably 20 to 45°C.

[0222] The pressure in the prepolymerisation reactor is not critical but must be high enough to keep the reaction mixture in the liquid phase. Thus, the pressure may be from 20 to 100 bar, for example from 30 to 70 bar.

[0223] In a preferred embodiment the prepolymerization is carried out as bulk slurry polymerization in liquid propylene, ie the liquid phase comprises mainly propylene, optionally with inert components dissolved therein. Furthermore, according to the present invention, as described above, an ethylene feed is employed during the prepolymerization.

[0224] Other components may also be added to the prepolymerization stage. Thus, as known in the art, hydrogen may be added to the prepolymerization stage to control the molecular weight of the polypropylene (pre-PP). In addition, antistatic additives may be used to prevent particles from adhering to each other or to the reactor walls.

[0225] Exact control of the prepolymerization conditions and reaction parameters is within the skill of the art.

[0226] Due to the process conditions in the prepolymerization defined above, a mixture (MI) of the single site catalyst (SSC) produced in the prepolymerization reactor (PR) and the polypropylene (pre-PP) is preferably obtained. Preferably, the single site catalyst (SSC) is (finely) dispersed in the polypropylene (pre-PP). In other words, the single site catalyst (SSC) particles introduced in the prepolymerization reactor (PR) are split into smaller fragments which are uniformly distributed in the growing polypropylene (pre-PP). The size of the introduced single site catalyst (SSC) particles and of the obtained fragments are not essentially relevant for the present invention and are within the technical knowledge.

[0227] As mentioned above if a prepolymerization is used the mixture (MI) of single site catalyst (SSC) and polypropylene (pre-PP) produced in the prepolymerization reactor (PR) is transferred to the first reactor (R1) after said prepolymerization. Typically the total amount of polypropylene (pre-PP) in the final bimodal propylene terpolymer (PP) is rather low and typically does not exceed 5.0 wt.-%, more preferably does not exceed 4.0 wt.-%, yet more preferably is in the range of 0.5 to 4.0 wt.-%, like in the range of 1.0 to 3.0 wt.-%.

[0228] Propylene and other ingredients, such as single site catalyst (SSC), are introduced directly into the first polymerization reactor (R1) without using prepolymerization.

[0229] In one embodiment, the present invention relates to an α-nucleated single-phase propylene terpolymer composition (PC) as described above, obtainable by the process described herein, more preferably obtainable by the process described herein. All preferred embodiments and alternative positions given above and below for the α-nucleated single-phase propylene terpolymer composition (PC) are applicable mutatis mutandis to the α-nucleated single-phase propylene terpolymer composition (PC) of the embodiments of the present invention.

[0230] Catalyst system

[0231] The single-site catalyst according to the present invention may be any supported metallocene catalyst suitable for producing isotactic polypropylene.

[0232] Preferred are single site catalysts (SSC) comprising a metallocene complex, a cocatalyst system comprising a boron-containing cocatalyst and / or an aluminoxane cocatalyst and a silica support.

[0233] In particular, it is preferred that the single site catalyst (SSC) comprises

[0234] (i) A metallocene complex having the general formula (II)

[0235]

[0236] wherein each X is independently a σ-donor ligand,

[0237] L is a divalent bridge selected from -R'2C-, -R'2C-CR'2-, -R'2Si-, -R'2Si-SiR'2-, -R'2Ge-, wherein each R' is independently a hydrogen atom or a C1-C ... 20- a hydrocarbon group, or optionally two R' groups together can form a ring,

[0238] Each R 1 are independently identical or can be different and are hydrogen, a linear or branched C1-C6-alkyl group, a C 7-20 -Arylalkyl, C 7-20 -alkylaryl group or C 6-20 -aryl group or OY group, wherein Y is C 1-10 - a hydrocarbon group, and optionally two adjacent R 1 The groups can be part of a ring containing the phenyl carbon to which they are bonded,

[0239] Each R 2 are independently the same or can be different, and are CH2-R 8 Group, where R 8 H or a straight or branched C 1-6 -alkyl group, C 3-8 -cycloalkyl group, C 6-10 - an aryl group,

[0240] R 3 is a straight-chain or branched C1-C6-alkyl group, C 7-20 -Arylalkyl, C 7-20 -alkylaryl group or C6-C 20 - aryl group, R 4 C(R 9 )3 groups, wherein R 9 is a straight-chain or branched C1-C6-alkyl group,

[0241] R 5 is hydrogen or optionally contains one or more heteroatoms from Groups 14 to 16 of the Periodic Table. 20 - a hydrocarbon group;

[0242] R 6 is hydrogen or optionally contains one or more heteroatoms from Groups 14 to 16 of the Periodic Table. 20 - a hydrocarbyl group; or

[0243] R 5 and R 6 can together form a 5-membered saturated carbocyclic ring, which is optionally substituted by n R 10 Group substitution, n is 0 to 4;

[0244] Each R 10 The same or different, and can be C1-C 20 -hydrocarbyl groups, or C1-C2-alkyl groups optionally containing one or more heteroatoms belonging to Groups 14 to 16 of the Periodic Table20 - a hydrocarbon group;

[0245] R 7 is H or a linear or branched C1-C6-alkyl group or optionally substituted by 1 to 3 R 11 a substituted aryl or heteroaryl group having 6 to 20 carbon atoms,

[0246] Each R 11 are independently identical or can be different and are hydrogen, a linear or branched C1-C6-alkyl group, a C 7-20 -Arylalkyl, C 7-20 -alkylaryl group or C 6-20 -aryl group or OY group, wherein Y is C 1-10 - a hydrocarbon group,

[0247] (ii) a cocatalyst system comprising a boron-containing cocatalyst and / or an aluminoxane cocatalyst, and

[0248] (iii) Silica support.

[0249] The term "σ-donor ligand" is well known to those skilled in the art, i.e., a group that binds to the metal via a σ bond. Thus, the anionic ligand "X" can independently be a halogen or selected from the group consisting of R', OR', SiR'3, OSiR'3, OSO2CF3, OCOR', SR', NR'2 or PR'2 groups, wherein R' is independently hydrogen, a linear or branched, cyclic or acyclic C1 to C 20 Alkyl, C2 to C 20 Alkenyl, C2 to C 20 Alkynyl, C3 to C 12 Cycloalkyl, C6 to C 20 Aryl, C7 to C 20 Aralkyl, C7 to C 20 Alkaryl, C8 to C 20 Aralkenyl, wherein the R' group can optionally contain one or more heteroatoms belonging to Groups 14 to 16. In a preferred embodiment, the anionic ligands "X" are identical and are halogen, such as Cl, or are methyl or benzyl.

[0250] Preferred monovalent anionic ligands are halogens, especially chlorine (Cl).

[0251] Preferred complexes of metallocene catalysts include:

[0252] Racemic-dimethylsilylenebis[2-methyl-4-(3',5'-dimethylphenyl)-5-methoxy-6-tert-butylinden-1-yl]zirconium dichloride,

[0253] Racemic-trans-dimethylsilylene[2-methyl-4-(4′-tert-butylphenyl)-inden-1-yl][2-methyl-4-(4′-tert-butylphenyl)-5-methoxy-6-tert-butylinden-1-yl]zirconium dichloride,

[0254] Racemic-trans-dimethylsilanylidene[2-methyl-4-(4′-tert-butylphenyl)-inden-1-yl][2-methyl-4-phenyl-5-methoxy-6-tert-butylinden-1-yl]zirconium dichloride,

[0255] Racemic-trans-dimethylsilylene[2-methyl-4-(3',5'-tert-butylphenyl)-1,5,6,7-tetrahydro-sym-indacene-1-yl][2-methyl-4-(3',5'-dimethyl-phenyl)-5-methoxy-6-tert-butylinden-1-yl]zirconium dichloride,

[0256] Racemic-trans-dimethylsilylene[2-methyl-4,8-bis-(4′-tert-butylphenyl)-1,5,6,7-tetrahydro-sym-indacene-1-yl][2-methyl-4-(3′,5′-dimethyl-phenyl)-5-methoxy-6-tert-butylinden-1-yl]zirconium dichloride,

[0257] Racemic-trans-dimethylsilylene[2-methyl-4,8-bis-(3',5'-dimethylphenyl)-1,5,6,7-tetrahydro-sym-indacene-1-yl][2-methyl-4-(3',5'-dimethylphenyl)-5-methoxy-6-tert-butylindene-1-yl]zirconium dichloride,

[0258] Racemic-trans-dimethylsilanylidene[2-methyl-4,8-bis-(3',5'-dimethylphenyl)-1,5,6,7-tetrahydro-sym-indacene-1-yl][2-methyl-4-(3',5'-5-di-tert-butyl-phenyl)-5-methoxy-6-tert-butylinden-1-yl]zirconium dichloride.

[0259] Particularly preferred is rac-trans-dimethylsilanylidene[2-methyl-4,8-bis-(3',5'-dimethylphenyl)-1,5,6,7-tetrahydro-sym-indacene-1-yl][2-methyl-4-(3',5'-dimethylphenyl)-5-methoxy-6-tert-butylinden-1-yl]zirconium dichloride.

[0260] The complex of the present invention is formed and the ligand required for the catalyst of the present invention is thus formed. It can be synthesized by any method, and a skilled organic chemist can design various synthesis schemes for the manufacture of necessary ligand materials. For example, WO2007 / 116034 discloses necessary chemistry. Synthesis schemes can also be generally found in WO 2002 / 02576, WO 2011 / 135004, WO 2012 / 084961, WO 2012 / 001052, WO 2011 / 076780, WO 2015 / 158790 and WO 2018 / 122134. With particular reference to WO 2019 / 179959, the most preferred catalyst of the present invention is described.

[0261] Catalyst

[0262] In order to form an active catalyst species, it is usually necessary to employ a promoter as is known in the art.

[0263] According to the present invention, a cocatalyst system comprising a boron-containing cocatalyst and / or an aluminoxane cocatalyst is used in combination with the metallocene catalyst complex defined above.

[0264] The aluminoxane cocatalyst may be an aluminoxane cocatalyst of formula (III):

[0265]

[0266] wherein n is generally 6 to 20 and R has the following meanings.

[0267] Aluminoxanes are formed upon partial hydrolysis of organoaluminum compounds, such as compounds having the formula AlR3, AlR2Y and Al2R3Y3, wherein R can be, for example, C1-C 10 Alkyl, preferably C1-C5 alkyl, or C3-C 10 Cycloalkyl, C7-C 12 Aralkyl or alkaryl and / or phenyl or naphthyl, and wherein Y can be hydrogen, halogen, preferably chlorine or bromine, or C1-C 10 The alkoxy group is preferably a methoxy group or an ethoxy group. The oxygen-containing aluminoxane obtained is usually not a pure compound but a mixture of oligomers of the formula (III).

[0268] The preferred aluminoxane is methylaluminoxane (MAO).Since the aluminoxanes used as cocatalysts according to the invention are not pure compounds due to the way they are prepared, the molar concentrations of the aluminoxane solutions hereinafter are based on their aluminum content.

[0269] According to the present invention, a boron-containing cocatalyst may also be used instead of the aluminoxane cocatalyst, or the aluminoxane cocatalyst may be used in combination with the boron-containing cocatalyst.

[0270] It will be appreciated by those skilled in the art that where a boron-based cocatalyst is employed, the complex is typically pre-alkylated by reacting the complex with an alkyl aluminum compound such as TIBA. This procedure is well known and any suitable aluminum alkyl may be used, such as Al(C 1-6 Preferred alkylaluminum compounds are triethylaluminum, triisobutylaluminum, triisohexylaluminum, tri-n-octylaluminum and tri-isooctylaluminum.

[0271] Alternatively, when a borate cocatalyst is used, the metallocene catalyst complex is in its alkylated form, ie for example a dimethyl or dibenzyl metallocene catalyst complex may be used.

[0272] Boron-based cocatalysts of interest include cocatalysts of formula (IV)

[0273] BY3(IV)

[0274] Wherein Y is the same or different and is a hydrogen atom, an alkyl group having 1 to about 20 carbon atoms, an aryl group having 6 to about 15 carbon atoms, an alkaryl, aralkyl, haloalkyl or haloaryl group, wherein each of the alkaryl, aralkyl, haloalkyl or haloaryl groups has 1 to 10 carbon atoms in the alkyl group and 6 to 20 carbon atoms in the aryl group, or fluorine, chlorine, bromine or iodine. Preferred options are trifluoroborane, triphenylborane, tris(4-fluorophenyl)borane, tris(3,5-difluorophenyl)borane, tris(4-fluoromethylphenyl)borane, tris(2,4,6-trifluorophenyl)borane, tris(pentafluorophenyl)borane, tris(tolyl)borane, tris(3,5-dimethyl-phenyl)borane, tris(3,5-difluorophenyl)borane and / or tris(3,4,5-trifluorophenyl)borane.

[0275] Tris(pentafluorophenyl)borane is particularly preferred.

[0276] However, preference is given to using borates, i.e. compounds containing borate 3+ ions. Such ionic promoters preferably contain non-coordinating anions, such as tetrakis(pentafluorophenyl)borate and tetraphenylborate. Suitable counterions are protonated amines or aniline derivatives, such as methylammonium, anilinium (the protonated form of aniline), dimethylammonium, diethylammonium, N-methylanilinium, diphenylammonium, N,N-dimethylanilinium, trimethylammonium, triethylammonium, tri-n-butylammonium, methyldiphenylammonium, pyridinium, p-bromo-N,N-dimethylanilinium or p-nitro-N,N-dimethylanilinium.

[0277] Surprisingly, it has been found that certain boron promoters are particularly preferred. Thus, preferred borates for use in the present invention include trityl ions. Thus, the use of N,N-dimethylammonium tetrakispentafluorophenylborate and Ph3CB(PhF5)4 and the like are particularly preferred.

[0278] Preferred cocatalysts are aluminoxanes, more preferably methylaluminoxane, combinations of aluminoxanes with alkylaluminum, boron or borate cocatalysts, and combinations of aluminoxanes with boron-based cocatalysts.

[0279] The catalyst system of the present invention is used in supported form. The particulate support material used is silicon dioxide or a mixed oxide, such as silicon dioxide-alumina, in particular silicon dioxide. Preferably, a silicon dioxide support is used. The skilled practitioner knows the procedures required for supporting the metallocene catalyst.

[0280] In a preferred embodiment, the catalyst system corresponds to ICS3 of WO 2020 / 239598 A1.

[0281] Products

[0282] In a last aspect, the present invention relates to an article, more preferably a film, comprising the α-nucleated single-phase propylene terpolymer composition (PC) according to anyone of the first two aspects in an amount of at least 75 wt%, more preferably at least 90 wt%, most preferably at least 95 wt%.

[0283] It is preferred that the article is a film, more preferably a cast film or a blown film.

[0284] The film may be a monolayer film. Alternatively, the film may be present as a monolayer in a multilayer film.

[0285] When the film is present as a single layer in a multilayer film, the multilayer film may be produced by any means known in the art.

[0286] It is preferred that the film has a thickness in the range of 5 to 100 μm, more preferably in the range of 10 to 80 μm, most preferably in the range of 20 to 70 μm.

[0287] The film according to the present invention preferably has a clarity value determined according to ASTM D1003 in the range of 98.0 to 100%, more preferably in the range of 99.0 to 100%, most preferably in the range of 99.5 to 100%.

[0288] The film according to the present invention preferably has a haze value determined according to ASTM D1003 in the range of 0.0 to 4.0%, more preferably in the range of 0.0 to 3.0%, most preferably in the range of 0.0 to 2.5%.

[0289] The film according to the present invention preferably has a seal initiation temperature (SIT) in the range of 100 to 125°C, more preferably in the range of 102 to 120°C, most preferably in the range of 103 to 117°C.

[0290] The film according to the present invention preferably has a seal end temperature (SET) in the range of 115 to 130°C, more preferably in the range of 120 to 128°C, most preferably in the range of 123 to 127°C.

[0291] The difference between the seal end temperature (SET) and the seal initiation temperature (SIT) of the film according to the present invention is preferably in the range of 10 to 25°C, more preferably in the range of 13 to 22°C, most preferably in the range of 15 to 20°C.

[0292] The difference between the melting temperature of the α-nucleated single-phase propylene terpolymer composition (PC) determined according to DSC analysis and the sealing initiation temperature (SIT) of the film according to the present invention is preferably in the range of 15 to 40 °C, more preferably in the range of 18 to 37 °C, most preferably in the range of 20 to 34 °C.

[0293] The film according to the invention preferably has a maximum sealing force in the range of 10 to 30N, more preferably in the range of 13 to 27N, most preferably in the range of 15 to 25N.

[0294] The film according to the present invention preferably has a hot tack measured according to ASTM F1921 -12-method B in the range of 2.0 to 5.0 N, more preferably in the range of 2.5 to 4.5 N, most preferably in the range of 3.0 to 4.0 N.

[0295] The film according to the present invention preferably has a hot tack temperature in the range of 95 to 115°C, more preferably in the range of 100 to 113°C, most preferably in the range of 104 to 111°C.

[0296] The film according to the present invention preferably has a 1.5N hot tack sealing process window in the range of 15 to 30°C, more preferably in the range of 17 to 28°C, most preferably in the range of 18 to 27°C.

[0297] The film according to the present invention preferably has a tensile storage modulus (E') in the range of 600 to 1700 MPa, more preferably in the range of 700 to 1600 MPa, most preferably in the range of 750 to 1500 MPa.

[0298] The film according to the present invention preferably has a dart impact strength measured according to ASTM D1709-A in the range of 40 to 550 g, more preferably in the range of 45 to 500 g, most preferably in the range of 50 to 450 g.

[0299] The film according to the invention preferably has a gloss at 60° in the machine direction measured according to ISO 2813 in the range of 120 to 170 GU, more preferably in the range of 130 to 160 GU, most preferably in the range of 135 to 150 GU.

[0300] The film according to the invention preferably has a gloss at 60° in the transverse direction measured according to ISO 2813 in the range of 120 to 170 GU, more preferably in the range of 130 to 160 GU, most preferably in the range of 135 to 150 GU.

[0301] Cast Film

[0302] In a particularly preferred embodiment the film according to the present invention is a cast film. In this embodiment it is further preferred that the α-nucleated single-phase propylene terpolymer composition (PC) has been visbroken and thus has the properties specified for the visbroken α-nucleated single-phase propylene terpolymer composition (PC) described above.

[0303] It is preferred that the cast film has a thickness in the range of 5 to 100 μm, more preferably in the range of 10 to 80 μm, most preferably in the range of 20 to 70 μm.

[0304] The cast film according to the present invention preferably has a clarity value determined according to ASTM D1003 in the range of 98.0 to 100%, more preferably in the range of 99.0 to 100%, most preferably in the range of 99.5 to 100%.

[0305] The cast film according to the present invention preferably has a haze value determined according to ASTM D1003 in the range of 0.0 to 1.0%, more preferably in the range of 0.0 to 0.7%, most preferably in the range of 0.0 to 0.5%.

[0306] The cast film according to the present invention preferably has a seal initiation temperature (SIT) in the range of 100 to 120°C, more preferably in the range of 102 to 115°C, most preferably in the range of 103 to 110°C.

[0307] The cast film according to the present invention preferably has a sealing end temperature (SET) in the range of 115 to 130°C, more preferably in the range of 120 to 128°C, most preferably in the range of 123 to 127°C.

[0308] The difference between the sealing end temperature (SET) and the sealing initiation temperature (SIT) of the cast film according to the present invention is preferably in the range of 10 to 25°C, more preferably in the range of 13 to 22°C, most preferably in the range of 15 to 20°C.

[0309] The difference between the melting temperature of the α-nucleated single-phase propylene terpolymer composition (PC) determined according to DSC analysis and the sealing initiation temperature (SIT) of the cast film according to the present invention is preferably in the range of 25 to 40 °C, more preferably in the range of 28 to 37 °C, most preferably in the range of 30 to 34 °C.

[0310] The cast film according to the present invention preferably has a maximum sealing force in the range of 10 to 25N, more preferably in the range of 13 to 22N, most preferably in the range of 15 to 20N.

[0311] The cast film according to the present invention preferably has a hot tack measured according to ASTM F1921 -12-Method B in the range of 2.0 to 5.0 N, more preferably in the range of 2.5 to 4.5 N, most preferably in the range of 3.0 to 4.0 N.

[0312] The cast film according to the present invention preferably has a hot sticking temperature in the range of 95 to 115°C, more preferably in the range of 100 to 110°C, most preferably in the range of 104 to 106°C.

[0313] The cast film according to the present invention preferably has a 1.5N hot tack sealing process window in the range of 20 to 30°C, more preferably in the range of 22 to 28°C, most preferably in the range of 23 to 27°C.

[0314] The cast film according to the present invention preferably has a tensile storage modulus (E') in the range of 600 to 1500 MPa, more preferably in the range of 700 to 1200 MPa, most preferably in the range of 750 to 1000 MPa.

[0315] The cast film according to the present invention preferably has a dart impact strength measured according to ASTM D1709-A in the range of 350 to 550 g, more preferably in the range of 380 to 500 g, most preferably in the range of 410 to 450 g.

[0316] Blown Film

[0317] In another particularly preferred embodiment, the film according to the present invention is a cast film. In this embodiment, it is further preferred that the α-nucleated single-phase propylene terpolymer composition (PC) is not visbroken and thus has the properties specified for the non-visbroken α-nucleated single-phase propylene terpolymer composition (PC) described above.

[0318] It is preferred that the blown film has a thickness in the range of 5 to 100 μm, more preferably in the range of 10 to 80 μm, most preferably in the range of 20 to 70 μm.

[0319] The blown film according to the present invention preferably has a clarity value determined according to ASTM D1003 in the range of 98.0 to 100%, more preferably in the range of 99.0 to 100%, most preferably in the range of 99.5 to 100%.

[0320] The blown film according to the present invention preferably has a haze value determined according to ASTM D1003 in the range of 0.0 to 4.0%, more preferably in the range of 0.0 to 3.0%, most preferably in the range of 0.0 to 2.5%.

[0321] The blown film according to the present invention preferably has a sealing initiation temperature (SIT) in the range of 110 to 125°C, more preferably in the range of 112 to 120°C, most preferably in the range of 113 to 117°C.

[0322] The difference between the melting temperature of the α-nucleated single-phase propylene terpolymer composition (PC) determined according to DSC analysis and the sealing initiation temperature (SIT) of the blown film according to the present invention is preferably in the range of 15 to 30 °C, more preferably in the range of 18 to 27 °C, most preferably in the range of 20 to 24 °C.

[0323] The blown film according to the present invention preferably has a maximum sealing force in the range of 15 to 30N, more preferably in the range of 18 to 27N, most preferably in the range of 20 to 25N.

[0324] The blown film according to the present invention preferably has a hot tack measured according to ASTM F1921 -12-Method B in the range of 2.0 to 5.0 N, more preferably in the range of 2.5 to 4.5 N, most preferably in the range of 3.0 to 4.0 N.

[0325] The blown film according to the present invention preferably has a hot sticking temperature in the range of 100 to 115°C, more preferably in the range of 105 to 113°C, most preferably in the range of 108 to 111°C.

[0326] The blown film according to the present invention preferably has a 1.5N hot tack sealing process window in the range of 15 to 25°C, more preferably in the range of 17 to 23°C, most preferably in the range of 18 to 22°C.

[0327] The blown film according to the present invention preferably has a tensile storage modulus (E') in the range of 1000 to 1700 MPa, more preferably in the range of 1200 to 1600 MPa, most preferably in the range of 1300 to 1500 MPa.

[0328] The blown film according to the present invention preferably has a dart impact strength measured according to ASTM D1709-A in the range of 40 to 60 g, more preferably in the range of 45 to 57 g, most preferably in the range of 50 to 55 g.

[0329] The blown film according to the present invention preferably has a gloss at 60° in the machine direction measured according to ISO 2813 in the range of 120 to 170 GU, more preferably in the range of 130 to 160 GU, most preferably in the range of 135 to 150 GU.

[0330] The blown film according to the present invention preferably has a gloss at 60° in the transverse direction measured according to ISO 2813 in the range of 120 to 170 GU, more preferably in the range of 130 to 160 GU, most preferably in the range of 135 to 150 GU.

[0331] All alternative positions provided above for the α-nucleated single-phase propylene terpolymer composition (PC) in the first or second aspect are applicable mutatis mutandis to the articles according to aspects of the invention.

[0332] Examples

[0333] A. Measurement Method

[0334] Unless defined otherwise, the following definitions of terms and assays apply to the above general description of the invention including the claims, as well as to the following examples.

[0335] Quantification of microstructure by NMR spectroscopy

[0336] Quantitative nuclear magnetic resonance (NMR) spectroscopy was used to quantify the comonomer content of the polymers.

[0337] Use for 1 H and 13 Quantitative measurements were recorded in the melt on a Bruker Avance III 500 NMR spectrometer operating at 500.13 and 125.76 MHz, respectively. 13 C{ 1 H} NMR spectroscopy. Nitrogen was used for all pneumatic devices and the temperature was 180 °C. 13All spectra were recorded using a C-optimized 7 mm magic angle spinning (MAS) probe. Approximately 200 mg of material was loaded into a 7 mm outer diameter zirconium oxide MAS rotor and spun at 4 kHz. This setup was chosen primarily for the high sensitivity required for rapid identification and accurate quantification {klimke06, parkinson07, castignolles09}. Standard single pulse excitation was used with a short recycle delay of 3 s using NOE {pollard04, klimke06} and RS-HEPT decoupling scheme {fillip05, griffin07}. A total of 1024 (1k) transients were collected for each spectrum.

[0338] Quantitative 13 C{ 1 H} NMR spectra were processed, integrated and relevant quantitative properties determined from the integration. All chemical shifts were internally referenced to the methyl isotactic pentad (mmmm) at 21.85 ppm.

[0339] A characteristic signal {brandolini01} corresponding to the incorporation of 1-butene was observed, and the comonomer content was quantified.

[0340] The amount of isolated 1-butene incorporated into the PBP sequence was quantified using the integration of the αB2 site at 43.6 ppm and taking into account the number of reported sites per comonomer:

[0341] B=I αB2 / 2

[0342] The amount of 1-butene incorporated continuously in the PBBP sequence was quantified using the integration of the ααB2B2 sites at 40.5 ppm and taking into account the number of reporter sites for each comonomer:

[0343] BB=2*I ααB2B2

[0344] In the presence of BB, the B value must be corrected for the effect of the αB2 site generated by the BB:

[0345] B=(I αB2 / 2)-BB / 2

[0346] The total 1-butene content is calculated based on the sum of isolated and continuously incorporated 1-butene:

[0347] B 总 =B+BB

[0348] A characteristic signal corresponding to the incorporation of ethylene {brandolini01} was observed and the comonomer content was quantified.

[0349] The amount of isolated ethylene incorporated in the PEP sequence was quantified using the integration of the Sββ site at 24.3 ppm and taking into account the number of reporter sites per comonomer:

[0350] E=I Sββ

[0351] If a characteristic signal corresponding to the continuous incorporation of ethylene in the PEE train is observed, quantification is performed using the Sβδ site at 27.0 ppm:

[0352] EE=I Sβδ

[0353] Characteristic signals {resconi00} corresponding to regio defects were observed. The presence of isolated 2,1-erythro regio defects was indicated by the presence of two methyl sites at 17.7 and 17.2 ppm, by the presence of a methylene site at 42.4 ppm, and confirmed by other characteristic sites. The presence of 2,1 regio defects adjacent to ethylene units was indicated by two unequal Sαβ signals at 34.8 ppm and 34.4 ppm, respectively, and Tγγ at 33.7 ppm.

[0354] The amount of isolated 2,1-erythro regio defects (P 21e孤立的 ) using the integration of the methylene sites at 42.4 ppm (I e9 ) to quantify:

[0355] P 21e孤立的 =I e9

[0356] If present, the methine site (I) at 33.7 ppm was used. Tγγ ) to quantify the amount of 2,1 regio defects adjacent to ethylene (P E21 ):

[0357] P E21 =I Tγγ

[0358] The total ethylene content was then calculated based on the sum of isolated, continuously incorporated, and adjacent to 2,1 regio defects:

[0359] E 总 =E+EE+P E21

[0360] The amount of propylene is quantified based on the Sαα methylene site at 46.7 ppm, including all additional propylene units not covered by Sαα, e.g., factor 3*P 21e孤立的 Three missing propylene units from an isolated 2,1-erythro regiodefect were considered:

[0361] P 总 =I Sαα +3*P 21e孤立的 +B+0.5*BB+E+0.5*EE+2*P E21

[0362] Then, the total mole fraction of 1-butene and ethylene in the polymer was calculated as follows:

[0363] fB=B 总 / (E 总 +P 总 +B 总 )

[0364] fE=E 总 / (E 总 +P 总 +B 总 )

[0365] Calculate the mole percentage of comonomer incorporation from the mole fraction:

[0366] B [mol %] = 100 * fB

[0367] E[mol%]=100*fE

[0368] Calculate the weight percent of comonomer incorporation from the mole fraction:

[0369] B [weight %] = 100 * (fB * 56.11) / ((fE * 28.05) + (fB * 56.11) + ((1 - (fE + fB)) * 42.08))

[0370] E [weight %] = 100 * (fE * 28.05) / ((fE * 28.05) + (fB * 56.11) + ((1 - (fE + fB)) * 42.08))

[0371] The mole percentage of isolated 2,1-erythro regio defects was quantified relative to all propylene:

[0372] [21e] mol% = 100*P 21e孤立的 / P 总

[0373] The mole percentage of 2,1 regio defects adjacent to ethylene was quantified relative to all propylene:

[0374] [E21] mol% = 100*P E21 / P 总

[0375] 2.1 The total amount of defects is quantified as follows:

[0376]

[21] mol% = [21e] + [E21]

[0377] No characteristic signals {resconi00} corresponding to other types of regional defects (2,1-threo, 3,1 insertion) were observed.

[0378] Literature (as mentioned above):

[0379] klimke06 Klimke,K.,Parkinson,M.,Piel,C.,Kaminsky,W.,Spiess,

[0380] HW, Wilhelm, M., Macromol. Chem. Phys. 2006; 207:382.

[0381] parkinson07 Parkinson,M.,Klimke,K.,Spiess,HW,Wilhelm,M.,

[0382] Macromol. Chem. Phys. 2007;208:2128.

[0383] pollard04 Pollard,M.,Klimke,K.,Graf,R.,Spiess,HW,Wilhelm,M.,

[0384] Sperber,O.,Piel,C.,Kaminsky,W.,Macromolecules 2004;37:813.

[0386] filip05 Filip,X.,Tripon,C.,Filip,C.,J.Mag.Resn.2005,176,239

[0387] griffin07 Griffin,JM,Tripon,C.,Samoson,A.,Filip,C.,and Brown,

[0388] SP,Mag.Res.in Chem.2007 45,S1,S198.

[0389] castignolles09 Castignolles,P.,Graf,R.,Parkinson,M.,Wilhelm,M.,

[0390] Gaborieau,M.,Polymer 50(2009)2373.

[0391] resconi00 Resconi,L.,Cavallo,L.,Fait,A.,Piemontesi,F.,Chem.Rev.

[0392] 2000,100,1253.

[0393] brandolini01 AJBrandolini,DDHills, “NMR spectra of polymers and

[0394] polymer additives”, Marcel Deker Inc., 2000

[0395] Calculate the comonomer content of the second random terpolymer fraction (PP2):

[0396]

[0397] in

[0398] w(PP1) is the weight fraction [in wt. %] of the first random terpolymer fraction (PP1),

[0399] w(PP2) is the weight fraction [in wt. %] of the second random terpolymer fraction (PP2),

[0400] C(PP1) is the comonomer content [in mol %] of the first random terpolymer fraction (PP1),

[0401] C(PP) is the comonomer content [in mol %] of the propylene / ethylene / 1-butene random terpolymer (PP),

[0402] C(PP2) is the calculated comonomer content [in mol %] of the second random terpolymer fraction (R-PP2).

[0403] Melt flow rate

[0404] The melt flow rate (MFR) is determined according to ISO 1133 and is expressed in g / 10 min. The MFR indicates the fluidity and, therefore, the processability of a polymer. The higher the melt flow rate, the lower the viscosity of the polymer. The MFR2 of polypropylene is determined at a temperature of 230°C and a load of 2.16 kg.

[0405] Calculate the melt flow rate MFR2 (230°C) of the second random terpolymer fraction (PP2):

[0406]

[0407] in

[0408] w(PP1) is the weight fraction [in wt. %] of the first random terpolymer fraction (PP1),

[0409] w(PP2) is the weight fraction [in wt. %] of the second random terpolymer fraction (PP2),

[0410] MFR(PP1) is the melt flow rate MFR2 (230°C) [in g / 10 min] of the first random terpolymer fraction (PP1),

[0411] MFR(PP) is the melt flow rate MFR2 (230°C) [in g / 10 min] of the propylene / ethylene / 1-butene random terpolymer (PP),

[0412] MFR(PP2) is the calculated melt flow rate MFR2 (230°C) [in g / 10 min] of the second random terpolymer fraction (PP2).

[0413] Xylene soluble fraction at room temperature (XCS, wt. %): The amount of polymer soluble in xylene is determined according to ISO 16152; 5th edition; 2005-07-01 at 25°C.

[0414] DSC analysis, melting temperature (T m ) and heat of fusion (H m ), crystallization temperature (T c ) and heat of crystallization (H c ): Measurements were performed on 5 to 7 mg samples using a TA Instrument Q200 Differential Scanning Calorimeter (DSC). The DSC was run according to ISO 11357 / Part 3 / Method C2 with a heating / cooling / heating cycle in the temperature range of -30 to +225°C at a scanning rate of 10°C / min. The crystallization temperature (T c ) and heat of crystallization (H c ) is determined by the cooling step, while the melting temperature (T m ) and heat of fusion (H m ) is determined by the second heating step.

[0415] The glass transition temperature Tg was determined by dynamic mechanical analysis according to ISO 6721-7. Compression molded specimens (40×10×1 mm2) were heated between −100° C. and +150° C. at a heating rate of 2° C. / min and a frequency of 1 Hz. 3 ) are measured in torsion mode.

[0416] Haze and clarity are measured according to ASTM D1003 on cast or blown films having a thickness of 50 μm, the production of which is described below.

[0417] Tensile storage modulus (E')

[0418] In dynamic mechanical thermal analysis in tension mode, the sample is subjected to a constant load and an applied sinusoidal tensile strain. At low deformations, the material response remains in the linear viscoelastic region, which is independent of the strain amplitude.

[0419] The tensile storage modulus E′(1) is determined by the following equation:

[0420]

[0421] in

[0422] ΔF A is the magnitude of the measured dynamic force in Newtons

[0423] s A is the amplitude of the measured dynamic displacement in meters

[0424] L a is the distance between the fixtures, in meters

[0425] b is the width of the specimen, in meters

[0426] d is the thickness of the sample, in meters

[0427] δ is the measured phase angle in degrees.

[0428] The characterization of dynamic mechanical properties complies with ISO standards 6721-1, 6721-4, 6721-11. The measurements were carried out on a "Netzsch DMA242EArtemis" strain / stress controlled dynamic mechanical analyzer equipped with a tensile sample holder for rectangular specimen geometry. Rectangular specimens cut from the film were measured. Dynamic mechanical thermal analysis was carried out at a temperature in the range of -40°C to +150°C under an inert atmosphere, while cooling with liquid nitrogen and a heating rate of 2K / min. The test parameters used included a frequency of 1 Hz, a maximum dynamic applied stress of 1.70 MPa, a static load of 0.20 MPa, and a maximum strain of 0.20% in strain-stress control mode. "Proteus Thermal Analysis - Version 6.1.0" software was used for evaluation to calculate E' at 23°C.

[0429] References:

[0430] [1] "Dynamic mechanical analysis: a practical introduction" Kevin P. 2008by Taylor&Francis Group,LLC,Dynamic Testing and Instrumentation,71-76,2008

[0431] Hot tack was measured on a J&B Hot-Tack Tester according to a modified method based on ASTM F1921-12-Method B, on films of 50 μm or 40 μm thickness according to the production method.

[0432] Sample cutting machine:

[0433] The test specimens were cut into a width of 25 mm (± 0.5%) using a drum cutter or a strip cutter.

[0434] Test machine:

[0435] Sealing strip length: 50mm

[0436] Sealing strip width: 5mm

[0437] Sealing strip shape: flat

[0438] Sealing strip material: Brass-Nickel

[0439] Sealing strip coating:

[0440] Roughness of sealing strip: about 1 μm

[0441] Force measurement: piezoelectric force sensor

[0442] Temperature measurement: 2 independent heating systems

[0443] Thickness measuring equipment: (Accuracy according to ISO 4593:1993)

[0444] Position indicator (Heidenhain; model: ND 280)

[0445] Measuring probe (Heidenhain; model: MT 1281)

[0446] Measuring surface: Flat / Polished surface

[0447] Diameter of each face: 6.5mm

[0448] Conditioning of samples / test specimens:

[0449] All test specimens must be prepared in a standard atmosphere for conditioning and testing at 23°C (±2°C) and 50% (±10%) relative humidity.

[0450] Minimum conditioning time of the test specimen in standard atmosphere before testing: >16h.

[0451] Minimum storage time between extrusion and testing of film samples: >88h.

[0452] Sample preparation:

[0453] Specimen type: Parallel cut strips of 25 mm (width) x approximately 320 mm (length) are taken across the width of the sample.

[0454] Specimen orientation: longitudinal direction

[0455] The specimen (film) should be free of dust, fingerprints, wrinkles, folds, shrivelling or other obvious defects. The edges of the cut specimens should be smooth and free of notches.

[0456] Thickness measurement:

[0457] The thickness of the test specimen is measured in the sealed area.

[0458] Hot-bonding-sealing process:

[0459] The test should be carried out under the same atmospheric conditions as the conditioning.

[0460] Under defined conditions of temperature, contact time and pressure, the 5*50mm) to apply pressure to seal the prepared sample strip.

[0461] The specimen is folded between the seals with an automatic specimen folding device. The seals are closed, and after the preset sealing time has elapsed, the seals are opened and the heat seal is completed. After the selected cooling time has elapsed, the lower specimen fixture is moved downwards, pulling the specimen out. During this step, a force sensor attached to the upper specimen fixture measures the force. Afterwards, the failure mode is determined visually.

[0462] Standard test conditions:

[0463] Sealing time (1s)

[0464] Sealing pressure (0.15N / mm 2 )

[0465] Delay time (0.2s)

[0466] Clamp separation rate (200mm / s)

[0467] Number of samples: at least 3 samples at each temperature

[0468] If the measured values ​​for one temperature step show a significant deviation, an additional specimen is tested in this temperature step to ensure that the data point is an outlier. However, the number of specimens should always be uneven, but the total number should not exceed 7 tested specimens. Only after the outlier has been confirmed is it allowed to be eliminated from the measurement; however, deviations caused by other reasons must be taken into account.

[0469] Temperature step / interval: rise 5℃

[0470] (In case of a sharp increase / decrease between two temperature steps, the rise is 2°C)

[0471] The measurement was started at two temperature steps below 0.2 to 0.3N.

[0472] The measurement is stopped at the failure mode burn-through.

[0473] One failure mode with burn-through and two other failure modes are allowed, with only one additional temperature step.

[0474] A typical hot tack curve may require 25 to 50 specimens per material.

[0475] result:

[0476] The output of this method is a hot tack curve. The interpretation of the hot tack curve has always relied on the relationship between sealing force and sealing temperature.

[0477] Hot tack is defined as the maximum force at failure mode "peel". When three specimens / temperature steps are used, two "peel" failure modes and any other failure mode (except burn-through failure mode) are also allowed.

[0478] 1.5N hot-melt sealing process window To determine the hot tack seal initiation temperature, the measured hot tack force vs. sealing temperature was fit with a sigmoidal function.

[0479]

[0480] Where F is the average hot tack seal force, T is the sealing temperature, and p, w, and s are fitting parameters. After fitting, the hot tack seal initiation temperature is calculated by setting F equal to 1.5N.

[0481]

[0482] The hot tack process window ends at the temperature at which any failure mode other than adhesive peel or peel elongation is observed. Therefore, two temperatures are also reported:

[0483] The hot tack seal initiation temperature [°C] is shown in Table 2 as the hot tack force exceeding 1.5 N (IT)

[0484] The hot tack sealing end temperature [°C] is shown in Table 2 as the hot tack force exceeding 1.5N (ET)

[0485] Unlike ASTM F1921-12 Chapter 9, the test is performed after a cooling time of 200 ms. The end of the measurement described in ASTM F1921-12 Chapter 9.8 (stop the test after determining the hot tack) is not considered. Instead, the test is considered to be over after the thermal failure of the film. In addition to the failure mode evaluation described in the standard, additional failure modes are used.

[0486] Sealing range tests (SIT, maximum sealing force and SET)

[0487] This method is used to determine the sealing window (sealing temperature range) of a film. The procedure is similar to the hot tack test and is performed in the same machine. In contrast to the hot tack, the determined sealing range corresponds to the strength of the seal after cooling (delay time 30 s). The conditions used are as follows:

[0488] Sealing time (1s)

[0489] Sealing pressure (0.4N / mm 2 )

[0490] Delay time (30s)

[0491] Clamp separation rate (42mm / s)

[0492] Sealing range = (sealing start temperature to sealing end temperature)

[0493] The measured results provide a quantitative useful indication of the seal strength of the film and show the temperature range for optimum sealing.

[0494] The lower limit (Seal Initiation Temperature - SIT) is the sealing temperature at which the average sealing force is measured ≥ 5 N. The upper limit (Seal End Temperature - SET) is determined as the first sealing temperature at which at least two specimens show a burn-through failure mode. The maximum sealing force corresponds to the highest sealing force measured.

[0495] The temperature interval is set to 5°C by default, but when the curve shows a sharp increase or decrease in force between two temperature steps, the temperature interval can be reduced to 1°C. This is done to show a better curve profile.

[0496] Unlike ASTM F1921-12, the test parameters sealing pressure, cooling time and test speed were modified. The force / temperature curve was continued until the membrane thermally failed. In addition to the failure mode evaluation described in the standard, additional failure modes were used.

[0497] DDI

[0498] ISO 7765-1:1988 / Method A

[0499] This test method covers the determination of the energy to cause membrane failure under specified conditions of impact of a free-falling dart from a specified height which will cause 50% of the test specimens to fail (Step Method A). Uniform missile mass increments are used during the test and after each specimen is tested, the missile weight is reduced or increased by uniform increments depending on the result (failure or non-failure) observed for the specimen.

[0500] Standard conditions:

[0501] Adjustment time: >96h

[0502] Test temperature: 23℃

[0503] Dart head material: phenolic resin

[0504] Dart diameter: 38mm

[0505] Drop height: 660mm

[0506] result:

[0507] Impact failure mass [g]

[0508] Minimum thickness [mm]

[0509] Maximum thickness [mm]

[0510] Tests according to ISO 7765-1:1988 / Method A were conducted on films having the indicated thickness, produced as described below under "Examples" and reported in grams (g).

[0511] The DDI per unit thickness (in grams / micrometer) is calculated by dividing the DDI (in grams) by the thickness of the film (in micrometers).

[0512] Gloss at 60° is measured according to ISO 2813.

[0513] B. Examples

[0514] For all examples, the catalyst used in the polymerization process is trans-dimethylsilylene [2-methyl-4,8-bis (3,5-dimethylphenyl) -1,5,6,7-tetrahydro-sym-indacene-1-yl] [2-methyl-4- (3,5-dimethylphenyl) -5-methoxy-6-tert-butylinden-1-yl] zirconium dichloride, as disclosed in WO 2019 / 179959 A1 as MC-2. The production of the supported metallocene catalyst is similar to IE2 in WO 2019 / 179959 A1.

[0515] PP-1 was polymerised according to the conditions given in Table 1 (note: the MFR2, C2 and C4 contents given after reactor R2 are properties of the GPR fraction and were calculated from the values ​​measured after the loop reactor (i.e. PP1) and in the final pellets (i.e. PP) using appropriate mixing rules).

[0516] Table 1: Polymerization conditions of propylene / ethylene / 1-butene terpolymer PP-1

[0517]

[0518] Blown films (RE1, IE1 and CE1) and cast films (RE2, IE2 and CE2) were prepared from PP-1 according to the formulations given in Table 2. Compounding was carried out on a ZSK 18 twin screw extruder, operating at 210°C with a production rate of 7 kg / h. For the cast film examples, the MFR2 was adjusted to about 30 g / 10 min by visbreaking with a peroxide visbreaking agent (DHBP). The amount of peroxide required to achieve such an MFR2 result can be determined directly by a person skilled in the art.

[0519] Blown films were prepared on a Collin 30 laboratory scale blown film line. The melt temperature was 210°C, the film thickness was 50 μm, the BUR was 1:2.5, and the uptake speed was 7 m / min. Cast films were prepared on a Collin 30 laboratory scale cast film line. The melt temperature was 250°C, the film thickness was 50 μm, and the uptake speed was 7 m / min. The properties of the blown and cast films produced by PP-1 are given in Table 3.

[0520] Table 2 Formulations of reference examples, embodiments of the present invention and comparative examples

[0521]

[0522] AO Irganox B215, antioxidant Irgafos 168 (tris(2,4-di-tert-butylphenyl)phosphite

[0523] ester, CAS No: 31570-04-4) and Irganox 1010 (pentaerythritol tetrakis(3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], CAS No: 6683-19-8), available from BASF SE.

[0524] SHT synthetic hydrotalcite, available from Kisuma Chemicals under the trade name DHT-4A.

[0525] NU1 pelletized blend, comprising 2,2'-methylenebis(2,6,-di-tert-butylphenyl) phosphate lithium salt as a major component, is available from Adeka Corporation under the trade name ADK STAB NA-71.

[0526] NU2 1,2,3-trideoxy-4,6:5,7-bis-O-((4-propylphenyl)methylene)nonitol, CAS No.:

[0527] 882073-43-0, available from Milliken & Company under the trade name Millad NX8000.

[0528] DHBP 2,5-dimethyl-2,5-di-(tert-butylperoxy)hexane, CAS No.: 78-63-7, available from

[0529] United Initiators obtain.

[0530] Table 3 Membrane properties of reference examples, examples of the present invention and comparative examples

[0531]

[0532] nm - not measured.

[0533] n / a - not available.

[0534] As can be seen from Table 3, the use of a particulate nucleating agent in the films of the present invention (both cast and blown films) results in a wider 1.5N hot tack sealing process window compared to films without nucleation (i.e., RE1 and RE2, respectively). On the other hand, the soluble nonitol nucleating agent results in a narrower 1.5N hot tack sealing process window than the reference examples (CE1 / CE2 vs. RE1 / RE2). It can also be seen that a similar trend is observed for the Tm-SIT parameter. For blown films, IE1 has greatly improved clarity relative to both RE1 and CE1. The blown and cast films of the present invention have significantly improved hot tack compared to both the reference example (no nucleation) and the comparative example (nonitol-nucleation). In addition, for blown films, IE1 has a much higher maximum sealing force than CE1 (i.e., nonitol-nucleated blown film). The same is true for the DDI in the blown film, where the reduction in DDI due to nucleation for IE1 is significantly lower than that for CE1. In many other characteristics (eg, haze, gloss, E'), the compositions of the invention show improvements over the non-nucleated reference examples that are similar to those observed in the comparative examples.

[0535] As has been demonstrated, the use of a particulate nucleating agent and the specific terpolymers of the present invention enables one skilled in the art to obtain compositions / films having significantly improved sealing and mechanical properties as well as optical properties (gloss) over non-nucleated compositions. Soluble nucleating agents have been demonstrated to be inferior to the specific nucleating agents of the present invention over a wide range of metrics.

Claims

1. An α-nucleated single-phase propylene terpolymer composition (PC) comprising: a) a propylene / ethylene / 1-butene random terpolymer (PP) having: i) in the range of 0.75 to 4.0 mol% by quantitative 13 Ethylene content (C2) determined by C-NMR spectroscopy; ii) in the range of 2.0 to 7.5 mol% by quantitative 13 1-Butene content (C4) determined by C-NMR spectroscopy; and iii) in the range of 0.1 to 1.5 mol% by quantitative 13 The content of 2,1-regio defects determined by C-NMR spectroscopy, and b) one or more alpha nucleating agents (NU), wherein at least one of the one or more alpha nucleating agents is a particulate alpha nucleating agent, wherein the total amount of the propylene / ethylene / 1-butene random terpolymer (PP) and the one or more α-nucleating agents (NU) amounts to at least 95 wt.-% of the total weight of the α-nucleated single-phase propylene terpolymer composition (PC), wherein the α-nucleated single-phase propylene terpolymer composition (PC) has each of the following properties: i) a melt flow rate (MFR2) determined according to ISO 1133 at 230°C under a load of 2.16 kg in the range of 1.0 to 35 g / 10 min; ii) a melting temperature in the range of 125 to 140° C. as determined by DSC analysis; and iii) Crystallization temperature determined by DSC analysis in the range of 95 to 115°C.

2. The α-nucleated single-phase propylene terpolymer composition (PC) according to claim 1, wherein at least one of the one or more α-nucleating agents (NU) is a particulate α-nucleating agent comprising a compound having a phosphate moiety.

3. The α-nucleated single-phase propylene terpolymer composition (PC) according to claim 2, wherein at least one of the one or more α-nucleating agents (NU) is a particulate α-nucleating agent comprising a granular α-nucleating agent having the structure [(Ar 1 O)(Ar 2 O)(O=)PO] n A compound of X, wherein Ar 1 and Ar 2 Each is independently selected from phenyl groups substituted by one or more C1 to C6 straight or branched alkyl groups, wherein Ar 1 and Ar 2 It can also be connected by a direct single bond, O or a C1 to C6 alkylene group n is 1 or 2, wherein if n=1, X is selected from the group consisting of Li, Na, K and Al(OH)2, and if n=2, X is selected from the group consisting of Mg, Ca and Al(OH).

4. The α-nucleated single-phase propylene terpolymer composition (PC) according to claim 3, wherein at least one of the one or more α-nucleating agents (NU) is a particulate α-nucleating agent comprising a compound selected from the group consisting of sodium di(4-tert-butylphenyl)phosphate, sodium 2,2'-methylene-bis-(4,6-di-tert-butylphenyl)phosphate, lithium 2,2'-methylene-bis-(4,6-di-tert-butylphenyl)phosphate and hydroxybis[2,2'-methylene-bis(4,6-di-tert-butylphenyl)phosphate]aluminum.

5. The α-nucleated single-phase propylene terpolymer composition (PC) according to any one of the preceding claims, wherein the melting temperature of the α-nucleated single-phase propylene terpolymer composition (PC) is 1.0 to 6.0 °C higher than the melting temperature of the propylene / ethylene / 1-butene random terpolymer (PP), both melting temperatures being determined according to DSC analysis, and / or The crystallization temperature of the α-nucleated single-phase propylene terpolymer composition (PC) is 5.0 to 15.0° C. higher than the crystallization temperature of the propylene / ethylene / 1-butene random terpolymer (PP), both crystallization temperatures being determined according to DSC analysis.

6. The α-nucleated single-phase propylene terpolymer composition (PC) according to any one of the preceding claims, wherein the propylene / ethylene / 1-butene random terpolymer (PP) comprises: a) 40 to 80 wt.-% of a first random terpolymer fraction (PP1) relative to the total weight of the propylene / ethylene / 1-butene random terpolymer (PP), the first random terpolymer fraction (PP1) having in the range of 0.75 to 4.0 mol-% a quantitative 13 The ethylene content (C2) determined by C-NMR spectroscopy and the ethylene content (C2) in the range of 1.0 to 5.0 mol % by quantitative 13 1-Butene content (C4) determined by C-NMR spectroscopy; and b) 20 to 60 wt.-% of a second random terpolymer fraction (PP2) relative to the total weight of the propylene / ethylene / 1-butene random terpolymer (PP), the second random terpolymer fraction (PP2) having in the range of 0.75 to 4.0 mol-% a quantitative 13 The ethylene content (C2) determined by C-NMR spectroscopy and the ethylene content (C2) in the range of 3.0 to 10.0 mol % by quantitative 13 1-Butene content (C4) determined by C-NMR spectroscopy, wherein the first random terpolymer fraction (PP1) and the second random terpolymer fraction (PP2) combined constitute at least 95 wt.-% of the total weight of the propylene / ethylene / 1-butene random terpolymer (PP).

7. The α-nucleated single-phase propylene terpolymer composition (PC) according to claim 6, wherein the ratio of the ethylene content of the propylene / ethylene / 1-butene random terpolymer (PP) to the ethylene content of the first random terpolymer fraction (PP1) ([C2(PP)] / [C2(PP1)]) is in the range of 0.70 to 1.30, both ethylene contents being determined by quantitative 13 C-NMR spectroscopy and expressed in mol %, and / or The ratio of the 1-butene content of the propylene / ethylene / 1-butene random terpolymer (PP) to the 1-butene content of the first random terpolymer fraction (PP1) ([C4(PP)] / [C4(PP1)]) is in the range of 1.00 to 2.00, and both 1-butene contents are determined by quantitative 13 The content was determined by C-NMR spectroscopy and is expressed in mol %.

8. The α-nucleated single-phase propylene terpolymer composition (PC) according to any of the preceding claims, wherein the propylene / ethylene / 1-butene random terpolymer (PP) has been formed by visbreaking a precursor propylene / ethylene / 1-butene random terpolymer (PP') using a visbreaking agent, more preferably using a peroxide radical generator.

9. An α-nucleated single-phase propylene terpolymer composition (PC) having: i) in the range of 0.75 to 4.0 mol% by quantitative 13 Ethylene content (C2) determined by C-NMR spectroscopy; ii) in the range of 2.0 to 7.5 mol% by quantitative 13 1-Butene content (C4) determined by C-NMR spectroscopy; iii) a melt flow rate (MFR2) measured according to ISO 1133 at 230°C under a load of 2.16 kg in the range of 1.0 to 35 g / 10 min; iv) a melting temperature in the range of 125 to 140°C as determined by DSC analysis; and v) a crystallization temperature determined by DSC analysis in the range of 95 to 115° C., The α-nucleated single-phase propylene terpolymer composition (PC) further comprises: a) 1.5N hot tack seal process window measured on 50 μm blown film samples in the range of 15 to 25°C, or b) 1.5N hot tack sealing process window measured on 50 μm cast film samples in the range of 20 to 30°C.

10. A process for producing an α-nucleated single-phase propylene terpolymer composition (PC) according to any one of the preceding claims, comprising the following steps: a) polymerizing propylene, ethylene and 1-butene comonomer units in the presence of a single site catalyst in a first polymerization reactor to produce a first polymerization mixture comprising the first random terpolymer fraction (PP1) and the single site catalyst, wherein the first polymerization reactor is preferably a slurry reactor, more preferably a loop reactor; b) withdrawing the first polymerization mixture from the first polymerization reactor and optionally carrying out steps c1) to c3) before step d); c1) transferring the first polymerization mixture to a second polymerization reactor, which is preferably a gas phase reactor; c2) polymerizing propylene, ethylene and 1-butene comonomer units in the presence of said single site catalyst in said second polymerization reactor to produce a second polymerization mixture comprising said first random terpolymer fraction (PP1), said second random terpolymer fraction (PP2) and said single site catalyst; c3) withdrawing the second polymerization mixture from the second polymerization reactor; as well as d) compounding the first polymerization mixture with the one or more alpha nucleating agents (NU), optionally with a visbreaking agent (V) and optionally with additional other additives to form the alpha-nucleated single-phase propylene terpolymer composition (PC), if steps c1) to c3) are absent, or compounding the second polymerization mixture with the one or more alpha nucleating agents (NU), optionally with a visbreaking agent (V) and optionally with additional other additives to form the alpha-nucleated single-phase propylene terpolymer composition (PC), if steps c1) to c3) are present.

11. The method according to claim 10, wherein the single active site catalyst comprises: (i) A metallocene complex having the general formula (II) wherein each X is independently a σ-donor ligand, L is a divalent bridge selected from -R'2C-, -R'2C-CR'2-, -R'2Si-, -R'2Si-SiR'2-, -R'2Ge-, wherein each R' is independently a hydrogen atom or a C1-C ... 20 - a hydrocarbon group, or optionally two R' groups together can form a ring, Each R 1 are independently identical or can be different and are hydrogen, a linear or branched C1-C6-alkyl group, a C 7-20 -Arylalkyl, C 7-20 -alkylaryl group or C 6-20 -aryl group or OY group, wherein Y is C 1-10 - a hydrocarbon group, and optionally two adjacent R 1 The groups can be part of a ring containing the phenyl carbon to which they are bonded, Each R 2 are independently the same or can be different, and are CH2-R 8 Group, where R 8 H or a straight or branched C 1-6 -alkyl group, C 3-8 -cycloalkyl group, C 6-10 - an aryl group, R 3 is a straight-chain or branched C1-C6-alkyl group, C 7-20 -Arylalkyl, C 7-20 -alkylaryl group or C6-C 20 - an aryl group, R 4 C(R 9 )3 groups, wherein R 9 is a straight-chain or branched C1-C6-alkyl group, R 5 is hydrogen or optionally contains one or more heteroatoms from Groups 14 to 16 of the Periodic Table. 20 - a hydrocarbon group; R 6 is hydrogen or optionally contains one or more heteroatoms from Groups 14 to 16 of the Periodic Table. 20 - a hydrocarbyl group; or R 5 and R 6 can together form a 5-membered saturated carbocyclic ring, which is optionally substituted by n R 10 Group substitution, n is 0 to 4; Each R 10 The same or different, and can be C1-C 20 -hydrocarbyl groups, or C1-C2-1-4-yl groups optionally containing one or more heteroatoms belonging to Groups 14 to 16 of the Periodic Table 20 - a hydrocarbon group; R 7 is H or a linear or branched C1-C6-alkyl group or optionally substituted by 1 to 3 R 11 a substituted aryl or heteroaryl group having 6 to 20 carbon atoms, Each R 11 are independently identical or can be different and are hydrogen, a linear or branched C1-C6-alkyl group, a C 7-20 -Arylalkyl, C 7-20 -alkylaryl group or C 6-20 -aryl group or OY group, wherein Y is C 1-10 - a hydrocarbon group, (ii) a cocatalyst system comprising a boron-containing cocatalyst and / or an aluminoxane cocatalyst, and (iii) Silica support.

12. The α-nucleated single-phase propylene terpolymer composition (PC) according to any one of claims 1 to 9, wherein the α-nucleated single-phase propylene terpolymer composition (PC) is obtainable by the process according to claim 10 or claim 11, more preferably obtainable by the process according to claim 10 or claim 11.

13. An article, more preferably a film, comprising the α-nucleated single-phase propylene terpolymer composition (PC) according to any one of claims 1 to 9 or 12 in an amount of at least 75 wt%, more preferably at least 90 wt%, most preferably at least 95 wt%.

14. The article according to claim 13, which is a blown film, having one or more of the following properties, preferably all of the following properties: a) a seal initiation temperature (SIT) in the range of 110 to 125°C, b) hot tack measured according to ASTM F1921-12-Method B in the range of 2.0 to 5.0 N, c) a dart impact strength measured according to ASTM D1709-A in the range of 40 to 60 g, d) a haze value determined according to ASTM D1003 in the range of 0.0 to 4.0%, e) a clarity value in the range of 98.0 to 100% as determined in accordance with ASTM D1003, and f) 1.5N hot tack sealing process window in the range of 15 to 25°C.

15. The article according to claim 13, which is a cast film having one or more of the following properties, preferably all of the following properties: a) a seal initiation temperature (SIT) in the range of 100 to 120°C, b) hot tack measured according to ASTM F1921-12-Method B in the range of 2.0 to 5.0 N, c) a dart impact strength measured according to ASTM D1709-A in the range of 350 to 550 g, d) a haze value determined according to ASTM D1003 in the range of 0.0 to 1.0%, e) a clarity value in the range of 98.0 to 100% as determined in accordance with ASTM D1003, and f) 1.5N hot tack sealing process window in the range of 20 to 30°C.

Citation Information

Patent Citations

  • Bridged BIS (indenyl) metallocene compounds

    WO2002002576A1

  • Metallocene compounds

    WO2007116034A1

  • catalysts

    WO2011076780A1

  • catalysts

    WO2011135004A2

  • catalysts

    WO2012001052A2